Reinforcement film
Patent Information
- Application Number
- JP2022036417
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-09
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-03-09
AI Technical Summary
Existing adhesive films used for reinforcing semiconductor element substrates and flexible devices face challenges in balancing flexibility and testability, leading to potential damage from repeated bending and difficulty in maintaining bonding integrity.
A reinforcing film comprising multiple adhesive films with varying properties, including a bending recovery angle of 35 degrees or more and light transmittance of 80% or more, arranged with gaps to accommodate different requirements of flexibility and testability, ensuring easy attachment to specific parts of the member.
The film provides enhanced flexibility and testability, reducing the risk of damage from bending and maintaining bonding integrity, while allowing easy application to specific areas of the substrate.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a reinforcing film. Preferably, the present invention relates to a reinforcing film suitable for optical components. [Background technology]
[0002] Adhesive films, which include a base layer and an adhesive layer, are used to reinforce components of various shapes.
[0003] For example, when bonding integrated circuits (ICs) or flexible printed circuit boards (FPCs) to a semiconductor substrate (e.g., a TFT substrate), thermocompression bonding is usually performed using an anisotropic conductive film (ACF). In some cases, when performing such thermocompression bonding, an adhesive film is pre-applied to the back side of the semiconductor substrate for reinforcement (for example, Patent Document 1).
[0004] Furthermore, in recent years, the manufacturing method for so-called flexible devices such as foldable devices and rollable devices, which are undergoing development, generally involves forming a release layer and a flexible film substrate on a support substrate such as glass, forming a TFT substrate on the film substrate, and then forming an organic EL layer on top of that. The support substrate is then peeled off to manufacture the flexible device, but because the flexible display layer is very thin, malfunctions can occur in the device due to handling. For this reason, an adhesive film is sometimes attached to the back side for reinforcement (for example, Patent Document 2).
[0005] Semiconductor element substrates and flexible devices may be repeatedly bent, and if the bending characteristics of the adhesive film bonded to the substrate are poor, the recovery after bending may deteriorate, or in the worst case, the film may break due to repeated bending. Specifically, when an adhesive film is bonded to a bent part (for example, the movable bending part of a folding member), when the adhesive film is bent at an angle, compressive stress acts on the inner diameter side of the bend and tensile stress acts on the outer diameter side of the bend. This causes stress strain in and around the bend, which can lead to damage to the semiconductor element substrate or flexible device.
[0006] Furthermore, when thermally bonding integrated circuits (ICs) or flexible printed circuit boards (FPCs) to semiconductor element substrates (such as TFT substrates), the bonding position is confirmed from the back of the substrate before bonding. After bonding, the film is inspected for any lifting or deformation. For this reason, the adhesive film bonded to the back of the substrate must be transparent.
[0007] As mentioned above, adhesive films that are attached to the back of a circuit board require good flexibility and good inspectability, but it is difficult to achieve both of these required characteristics simultaneously. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] Patent No. 5600039 [Patent Document 2] Patent No. 6376271 [Overview of the project] [Problems that the invention aims to solve]
[0009] As a result of repeated investigations into the above-mentioned conventional problems, the inventors of the present invention noticed that in semiconductor element substrates and flexible devices, the areas requiring good flexibility (for example, the area on which a flexible display element is mounted) and the areas requiring good inspectability (for example, the area on which a drive element is mounted) are often different. They then considered that if adhesive films with the required characteristics for each of these areas could be easily attached to their respective locations, the above-mentioned conventional problems could be solved.
[0010] The object of the present invention is to provide a reinforcing film for use in reinforcing a member, which allows for easy bonding of adhesive films having the required characteristics for parts of the member where good flexibility is required and parts of the member where good inspectability is required, to their respective locations.
Means for Solving the Problem
[0011] The reinforcing film according to an embodiment of the present invention is a reinforcing film in which two or more adhesive films are arranged with gaps between one release liner and one protective film, each of the two or more adhesive films includes a base material layer and an adhesive layer, the adhesive layer of the two or more adhesive films is directly laminated on the one release liner, the two or more adhesive films include an adhesive film (I) having at least one bending recovery angle of 35 degrees or more and an adhesive film (II) having a light transmittance of 80% or more at 550 nm.
[0012] In one embodiment, the storage modulus at 85°C of the adhesive layer of the adhesive film (I) is 1.0×10 5 less than Pa.
[0013] In one embodiment, the storage modulus at 170°C of the adhesive layer of the adhesive film (II) is 5.0×10 3 Pa or more and less than 5.0×10 5 Pa.
[0014] In one embodiment, the area of the adhesive film (I) is larger than the area of the adhesive film (II).
[0015] In one embodiment, the reinforcing film is a reinforcing film for an optical member.
Advantages of the Invention
[0016] According to the present invention, there is provided a reinforcing film used for reinforcing a member, which can easily bond adhesive films having required characteristics for each of a site where good flexibility of the member is required and a site where good inspection property is required at each location.
Brief Description of the Drawings
[0017] [Figure 1] This is a schematic cross-sectional view of a reinforcing film according to one embodiment of the present invention. [Figure 2] This is a schematic plan view of one embodiment of the reinforcing film of the present invention, showing the film after the release liner has been removed. [Figure 3] This is a schematic plan view of the reinforcing film of the present invention with the release liner removed, as shown in another embodiment. [Modes for carrying out the invention]
[0018] In this specification, the expression "(meth)acrylic" means "acrylic and / or methacrylic," the expression "(meth)acrylate" means "acrylate and / or methacrylate," the expression "(meth)allyl" means "allyl and / or methallyl," and the expression "(meth)acrolein" means "acrolein and / or methcrolein." In this specification, the expression "acid (salt)" means "acid and / or its salt." Examples of salts include alkali metal salts and alkaline earth metal salts, specifically, sodium salts and potassium salts.
[0019] ≪≪A. Reinforcement Film≫≫ A reinforcing film according to an embodiment of the present invention is a reinforcing film in which two or more adhesive films are arranged with a gap between one release liner and one protective film, wherein each of the two or more adhesive films includes a base layer and an adhesive layer, and the adhesive layers of the two or more adhesive films are directly laminated with the one release liner.
[0020] The number of adhesive films arranged to have a gap between one release liner and one protective film is two or more, preferably 2 to 10, more preferably 2 to 5, even more preferably 2 to 4, and particularly preferably 2 to 3.
[0021] Figure 1 shows a schematic cross-sectional view of one embodiment of the reinforcing film of the present invention. Figure 1 shows an embodiment in which two adhesive films are arranged with a gap between one release liner and one protective film. As shown in Figure 1, the reinforcing film 1000 is arranged between the release liner 100 and the protective film 200 with adhesive films 300a and 300b having a gap L. Adhesive film 300a includes a base layer 10a and an adhesive layer 20a. Adhesive film 300b includes a base layer 10b and an adhesive layer 20b.
[0022] The above-mentioned interval L is preferably 0.1 mm to 5.0 mm, more preferably 0.2 mm to 3.0 mm, even more preferably 0.3 mm to 2.0 mm, particularly preferably 0.5 mm to 1.5 mm, and most preferably 0.7 mm to 1.5 mm.
[0023] The adhesive films can be arranged in any suitable configuration as long as there is a gap between one release liner and one protective film, provided that the effects of the present invention are not impaired. In other words, two or more adhesive films can be arranged with gaps between them, corresponding to the arrangement of each part of the component to be bonded (e.g., an optical component) (particularly parts requiring good flexibility and parts requiring good inspectability).
[0024] Figure 2 is a schematic plan view of one embodiment of the reinforcing film of the present invention with the release liner removed. Figure 2 shows an embodiment in which two adhesive films are arranged with a gap between them. In Figure 2, adhesive film 300a and adhesive film 300b are arranged on the protective film 200 with a gap L between them.
[0025] Figure 3 is a schematic plan view of another embodiment of the reinforcing film of the present invention, with the release liner removed. Figure 3 shows an embodiment in which three adhesive films are arranged with gaps between them. In Figure 3, adhesive films 300a, 300b, and 300c are arranged on the protective film 200 with gaps L1 and L2 between them.
[0026] The reinforcing film according to the embodiment of the present invention may have any other suitable layer, as long as it does not impair the effects of the present invention. The other layer may be one type or two or more types. Examples of the other layer include an antistatic layer, which will be described later.
[0027] At least one of the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention is an adhesive film (I) having a bending recovery angle of 35 degrees or more. The bending recovery angle is preferably 40 degrees or more, more preferably 50 degrees or more, even more preferably 70 degrees or more, particularly preferably 100 degrees or more, and most preferably 120 degrees or more. The upper limit of the bending recovery angle is preferably 180 degrees or less. If the bending recovery angle of the adhesive film is within the above range, it can be suitably applied to parts where good flexibility is required. For example, it can effectively suppress the occurrence of creases and winding marks in the bendable and windable parts of a device that can be bent and wound. If the bending recovery angle is too small and outside the above range, it may not be applicable to parts where good flexibility is required. The method for measuring the bending recovery angle will be described later.
[0028] An adhesive film (I) having a bending recovery angle of 35 degrees or more can be realized, for example, by appropriately selecting the base layer (I) and the adhesive layer (I).
[0029] At least one of the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention is an adhesive film (II) having a light transmittance of 80% or more at 550 nm. The above light transmittance is preferably 83% or more, more preferably 85% or more, even more preferably 88% or more, and particularly preferably 90% or more. The upper limit of the above light transmittance is preferably 100% or less. If the above light transmittance of the adhesive film is within the above range, it can be preferably applied to parts where good inspectability is required. For example, good inspectability after IC bonding can be maintained. If the above light transmittance is too low and outside the above range, it may not be applicable to parts where good inspectability is required. The method for measuring the above light transmittance will be described later.
[0030] An adhesive film (II) having a light transmittance of 80% or more at 550 nm can be realized, for example, by appropriately selecting the substrate layer (II) and the adhesive layer (II).
[0031] The adhesive layer of the adhesive film (I) preferably has a storage modulus of 1.0 × 10 at 85°C. 5 Less than Pa, more preferably 8.0 × 10 4 It is less than Pa, and more preferably 5.0 × 10 4 It is less than Pa, and particularly preferably 2.0 × 10⁻⁶ 4 It is less than Pa. The lower limit of the storage modulus at 85°C is, in practice, preferably 1.0 × 10⁻⁶. 3 The storage modulus at 85°C is Pa or higher. If the storage modulus at 85°C is within the above range, it can be more preferably applied to parts where good flexibility is required. For example, it can better suppress the occurrence of creases and winding marks in the bendable and windable parts of a device that can be folded and wound. If the storage modulus at 85°C is too low and outside the above range, it may not be applicable to parts where good flexibility is required. The method for measuring the storage modulus at 85°C will be described later.
[0032] The adhesive layer of the adhesive film (II) preferably has a storage modulus of 5.0 × 10 at 170°C.3 above 5.0×10 Pa 5 and less than, more preferably 7.5×10 Pa 3 above 2.5×10 Pa 5 and less than, still more preferably 1.0×10 Pa 4 above 1.0×10 Pa 5 and less than. If the storage elastic modulus at 170°C is within the above range, it can be more preferably applied to a site where good inspection properties are required. For example, it can maintain better inspection properties after IC bonding. If the storage elastic modulus at 170°C is outside the above range, that is, if it is too high or too low outside the above range, for example, bubbles are likely to enter during IC bonding, etc., and there is a risk that it cannot be applied to a site where good inspection properties are required. The method for measuring the storage elastic modulus at 170°C will be described later.
[0033] The area of the adhesive film (I) (the total area when there are a plurality of adhesive films (I)) and the area of the adhesive film (II) (the total area when there are a plurality of adhesive films (II)) can be appropriately set according to the sizes of the sites where good flexibility and good inspection properties are required, respectively. For example, in the case of a device that can be bent or wound, typically, since the area of the site where a flexible display element is mounted (a site where good flexibility is required) is larger than the area of the site where a driving element is mounted (a site where good inspection properties are required), in such a case, the area of the adhesive film (I) (the total area when there are a plurality of adhesive films (I)) is preferably larger than the area of the adhesive film (II) (the total area when there are a plurality of adhesive films (II)).
[0034] In the embodiment of the present invention, the reinforcing film is preferably bonded to the member to be bonded (e.g., an optical member) after peeling off the release liner, and then the protective film is peeled off. Therefore, in order to facilitate the bonding operation, the peeling force (A) of the release liner is preferably smaller than the peeling force (B) of the protective film with respect to a common adhesive film. If the peeling force (A) of the release liner is greater than the peeling force (B) of the protective film with respect to a common adhesive film, there is a risk that delamination will occur between the protective film and the adhesive film when attempting to peel the release liner from the adhesive film.
[0035] The peeling force (A) of the peeling liner is preferably 0 gf / 25 mm to 10 gf / 25 mm, more preferably 0 gf / 25 mm to 8 gf / 25 mm, and even more preferably 0 gf / 25 mm to 5 gf / 25 mm.
[0036] The peel strength (B) of the protective film is preferably 2 gf / 25 mm or more and less than 15 gf / 25 mm, and more preferably 2.5 gf / 25 mm or more and less than 12 gf / 25 mm.
[0037] The reinforcing film according to the embodiment of the present invention can be used in various applications. In terms of being able to utilize the effects of the present invention more effectively, the reinforcing film according to the embodiment of the present invention is typically used as a reinforcing film for optical components. The reinforcing film according to the embodiment of the present invention can be suitably used in flexible devices such as bendable devices, foldable devices, and rollable devices that have movable bending portions.
[0038] ≪A-1. Adhesive Film≫ The reinforcing film according to an embodiment of the present invention includes two or more adhesive films. At least one of the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention is an adhesive film (I) having a bending recovery angle of 35 degrees or more, and at least one is an adhesive film (II) having a light transmittance of 80% or more at 550 nm.
[0039] The adhesive film includes a base material layer and an adhesive layer. That is, the adhesive film (I) includes a base material layer (I) and an adhesive layer (I), and the adhesive film (II) includes a base material layer (II) and an adhesive layer (II).
[0040] In addition to the base material layer and the adhesive layer, the adhesive film may have any other appropriate layer as long as the effects of the present invention are not impaired. The other layer may be only one type or two or more types. Examples of the other layer include an antistatic layer described later.
[0041] The thicknesses of the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention may be the same, or at least one may have a different thickness. From the viewpoint of ease of handling, etc., it is preferable that the thicknesses of the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention are the same.
[0042] <A-1-1. Base material layer> In this specification, when simply referred to as the "base material layer", it means including any of the base material layers included in the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention (that is, including both the base material layer (I) and the base material layer (II)).
[0043] The thickness of the base material layer is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, still more preferably 10 μm to 100 μm, particularly preferably 15 μm to 90 μm, and most preferably 20 μm to 85 μm. If the thickness of the base material layer is within the above range, the effects of the present invention can be more manifested.
[0044] Any suitable material can be used as the base layer material, as long as it can exhibit the effects of the present invention as a component of the adhesive film. Typical examples of such base layer materials include resin materials.
[0045] Examples of resin materials used as the base layer material include acrylic resins such as polyimide (PI), polyether ether ketone (PEEK), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), and polymethyl methacrylate (PMMA), as well as polycarbonate, triacetylcellulose (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), fully aromatic polyamide (aramid), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluororesin, cyclic olefin polymer (COP), and polycarbonate (PC). The resin material used as the base layer material may consist of only one type or two or more types.
[0046] In the reinforcing film according to the embodiment of the present invention, it is preferable that the base material layer (I) contained in the adhesive film (I) and the base material layer (II) contained in the adhesive film (II) have different physical properties and are made of different materials in order to better exhibit the effects of the present invention.
[0047] The base layer (I) has a Young's modulus of preferably 6.0 × 10 at 23°C. 7 Pa or higher, more preferably 1.0 × 10⁻⁶ 8 Pa or higher, and more preferably 5.0 × 10⁻⁶ 8 The pressure is Pa or higher, and particularly preferably 8.0 × 10⁻⁶ 8 The Pa level is above, and most preferably 1.0 × 10⁻⁶. 9 It is Pa or higher. The upper limit of the Young's modulus of the substrate layer (I) at 23°C is typically preferably 1.0 × 10⁻⁶. 11It is Pa or less. If the Young's modulus of the base layer (I) at 23°C is within the above range, the adhesive film (I) can be preferably applied to parts where good flexibility is required. For example, it can effectively suppress the occurrence of creases and winding marks in the bendable and windable parts of a bendable and windable device. If the Young's modulus of the base layer (I) at 23°C is too low, when the adhesive film (I) is bent at an angle, the tensile strength on the outer diameter side may not be sufficiently maintained against the compression on the inner diameter side, which may cause the thickness to change easily and may lead to lifting from the adherend. If the Young's modulus of the base layer (I) at 23°C is too high, the adhesive film (I) may not be easily deformable. The method for measuring Young's modulus will be described later.
[0048] In order to better demonstrate the effects of the present invention, the resin material used as the material for the substrate layer (I) is preferably at least one selected from polyimide (PI), polyethylene terephthalate (PET), and triacetylcellulose (TAC).
[0049] The substrate layer (II) preferably has a transmittance of 80% or more at 550 nm, more preferably 83% or more, even more preferably 85% or more, particularly preferably 88% or more, and most preferably 90% or more. If the transmittance of the substrate layer (II) at 550 nm is within the above range, the adhesive film (II) can be preferably applied to areas where good inspectability is required. For example, it can maintain better inspectability after IC bonding. If the transmittance of the substrate layer (II) at 550 nm is too high or too low outside the above range, it may not be applicable to areas where good inspectability is required. The method for measuring the transmittance at 550 nm will be described later.
[0050] In order to better demonstrate the effects of the present invention, polyethylene terephthalate (PET) is preferably used as the resin material for the base layer (II).
[0051] The base material layer may contain any appropriate additive as long as the effects of the present invention are not impaired. The base material layer may be subjected to any appropriate surface treatment as long as the effects of the present invention are not impaired.
[0052] <A-1-2. Adhesive layer> In this specification, when simply referred to as the "adhesive layer", it means any of the adhesive layers included in two or more adhesive films contained in the reinforcing film according to the embodiment of the present invention (that is, it includes both the adhesive layer (I) and the adhesive layer (II)).
[0053] The thickness of the adhesive layer is preferably 1 μm to 250 μm, more preferably 2 μm to 150 μm, still more preferably 3 μm to 100 μm, particularly preferably 5 μm to 50 μm, and most preferably 10 μm to 35 μm. If the thickness of the adhesive layer is within the above range, the effects of the present invention can be more manifested.
[0054] The adhesive layer is composed of an adhesive. As the adhesive constituting the adhesive layer, an acrylic adhesive is preferred.
[0055] The acrylic adhesive is formed from an acrylic adhesive composition.
[0056] The acrylic adhesive can thus be defined as being formed from an acrylic adhesive composition. This is because the acrylic adhesive cannot be directly specified by its structure since the acrylic adhesive composition undergoes a cross-linking reaction or the like by heating or ultraviolet irradiation to become an acrylic adhesive, and there is a situation (an "impossible and impractical situation") that it is approximately not practical. Therefore, by the definition of "being formed from an acrylic adhesive composition", the acrylic adhesive is properly specified as a "substance".
[0057] The acrylic adhesive has an adhesive strength to glass of preferably 5 N / 25 mm or more, more preferably 7 N / 25 mm or more, even more preferably 8 N / 25 mm or more, particularly preferably 10 N / 25 mm or more, and most preferably 15 N / 25 mm or more at 23°C, a peeling speed of 300 mm / min, and a peeling angle of 180 degrees. While a higher adhesive strength is generally preferable, considering the balance with other adhesive properties, it is preferably 50 N / 25 mm or less. By adjusting the adhesive strength within the above range, it can function favorably as a reinforcing film. The method for measuring the adhesive strength will be described later.
[0058] As for the method of forming the acrylic adhesive, any suitable method can be employed as long as it does not impair the effects of the present invention. For example, one such method of forming an acrylic adhesive is to apply an acrylic adhesive composition onto any suitable substrate, heat and dry as necessary, and cure as necessary to form the acrylic adhesive in a sheet form on the substrate.
[0059] Any suitable means can be used to apply the acrylic adhesive composition, as long as it does not impair the effects of the present invention. Examples of such application methods include the roll coating method, gravure roll coating method, reverse roll coating method, kiss roll coating method, dip roll coating method, bar coating method, roll brush coating method, spray coating method, knife coating method, air knife coating method, comma coating method, direct coating method, and die coating method.
[0060] The heating and drying of the acrylic adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. Examples of such heating and drying methods include heating to 60°C to 180°C, or performing an aging treatment at a temperature of approximately room temperature.
[0061] The curing of the acrylic adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. Examples of such curing means include heat, ultraviolet irradiation, laser irradiation, alpha-ray irradiation, beta-ray irradiation, gamma-ray irradiation, X-ray irradiation, and electron beam irradiation.
[0062] Typical methods for forming an acrylic adhesive from an acrylic adhesive composition include: (1) A method for forming a photocurable acrylic adhesive by a photocuring reaction of a photocurable acrylic adhesive composition containing an acrylic polymer (typically a partially polymerized acrylic product) prepared by polymerization (typically partial polymerization) using a photopolymerization initiator, (2) A method for forming a thermosetting acrylic adhesive by a crosslinking reaction of a thermosetting acrylic adhesive composition containing an acrylic polymer prepared by solution polymerization using a thermal polymerization initiator. These are some examples.
[0063] In other words, typical acrylic adhesives include, (1) A photocurable acrylic adhesive formed by the photocuring reaction of a photocurable acrylic adhesive composition containing an acrylic polymer (typically a partially polymerized acrylic product) (P1) prepared by polymerization (typically partial polymerization) using a photopolymerization initiator, (2) A thermosetting acrylic adhesive formed by a crosslinking reaction of a thermosetting acrylic adhesive composition containing an acrylic polymer (P2) prepared by solution polymerization using a thermal polymerization initiator, These are some examples.
[0064] [A-1-2-1. Acrylic polymer (P1)] One embodiment of the acrylic polymer is an acrylic polymer (P1) prepared by polymerization (typically partial polymerization) using a photoinitiator. Any suitable method can be used for polymerization using a photoinitiator, such as conventionally known methods, as long as it does not impair the effects of the present invention. Polymerization using a photoinitiator is typically carried out by irradiation with light such as UV.
[0065] The acrylic polymer (P1) is preferably an acrylic partial polymer (sometimes called an acrylic prepolymer). Unlike a complete polymer of the monomer component (preferably a polymer with a polymerization conversion rate of more than 95% by weight), the acrylic partial polymer is a partial polymer obtained by using the monomer component with a polymerization conversion rate of preferably 95% by weight or less.
[0066] The polymerization conversion rate of the acrylic partial polymer is preferably 70% by weight or less, more preferably 60% by weight or less, even more preferably 50% by weight or less, particularly preferably 40% by weight or less, and most preferably 35% by weight or less. The lower limit of the polymerization conversion rate of the acrylic partial polymer is preferably 1% by weight or more, more preferably 5% by weight or more.
[0067] The acrylic polymer (P1) is obtained by polymerizing the monomer component (M1). The monomer component (M1) referred to here does not include the crosslinking agent that may be included in the acrylic adhesive composition, as described later. When obtaining the acrylic polymer (P1) by polymerization, in addition to the monomer component (M1) and the photopolymerization initiator, any suitable additive may be used as long as it does not impair the effects of the present invention.
[0068] Acrylic polymer (P1) can thus be defined as something obtained by polymerizing monomer component (M1). This is because acrylic polymer (P1) is formed when monomer component (M1) undergoes a polymerization reaction, and it is impossible and impractical to directly identify acrylic polymer (P1) by its structure. Therefore, the definition "something obtained by polymerizing monomer component (M1)" appropriately identifies acrylic polymer (P1) as a "substance."
[0069] The acrylic polymer (P1) preferably has a Tg of -70°C to 50°C, more preferably -60°C to 40°C, even more preferably -55°C to 30°C, and particularly preferably -50°C to 20°C, in order to better exhibit the effects of the present invention. By adjusting the Tg of the acrylic polymer (P1) to the above specific range, the effects of the present invention can be better exhibited.
[0070] The Tg of an acrylic polymer (P1) is a value obtained from Fox's formula based on the Tg of the homopolymers of each monomer constituting the acrylic polymer (P1) and the weight fraction (weight-based copolymerization ratio) of the monomers. Fox's formula is a relationship between the Tg of a copolymer and the glass transition temperature Tgi of the homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg = Σ(Wi / Tgi)
[0071] In the Fox equation above, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (weight-based copolymerization ratio), and Tgi represents the glass transition temperature of the monomer i homopolymer (unit: K). The Tg of the homopolymer shall be the value specified in the publicly available documents.
[0072] For example, the following values can be used as the Tg of the homopolymer. n-butyl acrylate (BA): -55℃ Lauryl acrylate (LA): -23℃ 2-Ethylhexyl acrylate (2EHA): -70℃ 2-Hydroxyethyl acrylate (2HEA): -15℃ 4-Hydroxybutyl acrylate (4HBA): -40℃ N-vinyl-2-pyrrolidone (NVP): 80℃ Methyl methacrylate (MMA): 105℃
[0073] For homopolymers other than those exemplified above, the values listed in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) may be used. If multiple values are listed in the "Polymer Handbook," the conventional value shall be adopted. For monomers not listed in the "Polymer Handbook," the catalog values of the monomer manufacturers shall be adopted. For homopolymers of monomers not listed in the "Polymer Handbook" and for which the monomer manufacturers do not provide catalog values, the value obtained by the measurement method described in Japanese Patent Publication No. 2007-51271 shall be used.
[0074] The monomer component (M1) preferably comprises an alkyl (meth)acrylate (a1) and a polar group-containing monomer (b1). The alkyl (meth)acrylate (a1) may consist of only one type or two or more types. The polar group-containing monomer (b1) may consist of only one type or two or more types.
[0075] The alkyl group in the ester portion of alkyl (meth)acrylate (a1) (hereinafter sometimes referred to as "alkyl group in the ester portion") does not include alkyl groups containing hydroxyl groups or alkyl groups containing polar groups other than hydroxyl groups. Therefore, alkyl (meth)acrylate (a1) is clearly distinguished from polar group-containing monomer (b1).
[0076] The content of alkyl (meth)acrylate (a1) in the monomer component (M1) is preferably 40% to 99% by weight, more preferably 45% to 90% by weight, even more preferably 50% to 80% by weight, and particularly preferably 60% to 75% by weight, in order to better exhibit the effects of the present invention.
[0077] The alkyl group of the ester portion is preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 18 carbon atoms, even more preferably an alkyl group having 2 to 16 carbon atoms, particularly preferably an alkyl group having 3 to 14 carbon atoms, and most preferably an alkyl group having 6 to 14 carbon atoms, in order to better express the effects of the present invention.
[0078] The alkyl group in the ester portion is preferably a linear alkyl group, as this allows for better expression of the effects of the present invention. Here, "linear" includes both linear and branched alkyl groups.
[0079] Examples of alkyl(meth)acrylates (a1) in which the alkyl group of the ester portion is a chain alkyl group having 1 to 20 carbon atoms include methyl(meth)acrylate, ethyl(meth)acrylate, propyl(meth)acrylate, isopropyl(meth)acrylate, n-butyl(meth)acrylate, isobutyl(meth)acrylate, s-butyl(meth)acrylate, pentyl(meth)acrylate, isopentyl(meth)acrylate, hexyl(meth)acrylate, heptyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, octyl(meth)acrylate, and Examples include sooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate.
[0080] In order to better express the effects of the present invention, the alkyl (meth)acrylate (a1) that can be contained in the monomer component (M1) preferably has a glass transition temperature Tg of its homopolymer (homopolymer) of -10°C or lower, more preferably -12°C or lower, even more preferably -15°C or lower, particularly preferably -18°C or lower, and most preferably -20°C or lower. The lower limit of the above glass transition temperature Tg is preferably -80°C or higher. The glass transition temperature Tg of the homopolymer (homopolymer) of the alkyl (meth)acrylate (a1) that can be contained in the monomer component (M1) may affect the adhesive properties of the acrylic polymer (P1). By using an alkyl (meth)acrylate (a1) as the alkyl (meth)acrylate (a1) that has a glass transition temperature Tg of its homopolymer (homopolymer) within the above range, the effects of the present invention can be better expressed.
[0081] Here, the glass transition temperature (Tg) of the homopolymer (a1) of the alkyl (meth)acrylate that may be contained in the monomer component (M1) can be a value described in publicly available documents. For example, the value described in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. If multiple values are described in the "Polymer Handbook," the conventional value should be adopted. For alkyl (meth)acrylates not described in the "Polymer Handbook," the catalog value from the monomer manufacturer should be adopted. For alkyl (meth)acrylate homopolymers that are not described in the "Polymer Handbook" and for which the monomer manufacturer does not provide a catalog value, the value obtained by the measurement method described in Japanese Patent Publication No. 2007-51271 should be used.
[0082] In order to further enhance the effects of the present invention, the alkyl (meth)acrylate (a1) that may be included in the monomer component (M1) preferably includes alkyl (meth)acrylate (a1-1) whose homopolymer (homopolymer) has a glass transition temperature Tg in the range of -40°C to -10°C (preferably -35°C to -15°C, more preferably -30°C to -20°C). By including alkyl (meth)acrylate (a1-1) in alkyl (meth)acrylate (M1), the effects of the present invention can be further enhanced.
[0083] Examples of alkyl (meth)acrylate (a1-1) include lauryl acrylate (LA) (whose homopolymer has a glass transition temperature Tg = -23°C).
[0084] The content of alkyl(meth)acrylate (a1-1) in the total amount of alkyl(meth)acrylate (a1-1) that can be contained in the monomer component (M1) is preferably 0% to 90% by weight, more preferably 10% to 80% by weight, even more preferably 20% to 70% by weight, and particularly preferably 30% to 60% by weight, in order to better express the effects of the present invention.
[0085] The content of alkyl (meth)acrylate (a1-1) in the total amount of monomer component (M1) is preferably 0% to 70% by weight, more preferably 10% to 60% by weight, even more preferably 20% to 50% by weight, and particularly preferably 30% to 45% by weight, in order to better express the effects of the present invention.
[0086] In order to further enhance the effects of the present invention, the alkyl (meth)acrylate (a1) that may be included in the monomer component (M1) preferably includes alkyl (meth)acrylate (a1-2) whose homopolymer (homopolymer) has a glass transition temperature Tg in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C). By including alkyl (meth)acrylate (a1-2) in alkyl (meth)acrylate (M1), the effects of the present invention can be further enhanced.
[0087] Examples of alkyl (meth)acrylates (a1-2) include 2-ethylhexyl acrylate (2EHA) (the glass transition temperature Tg = -70°C of its homopolymer).
[0088] The content ratio of alkyl (meth)acrylate (a1-2) in the total amount of alkyl (meth)acrylate (a1) that can be contained in the monomer component (M1) is preferably 20% to 90% by weight, more preferably 30% to 80% by weight, even more preferably 40% to 70% by weight, and particularly preferably 50% to 65% by weight, in order to better express the effects of the present invention.
[0089] The content of alkyl (meth)acrylate (a1-2) in the total amount of monomer component (M1) is preferably 10% to 100% by weight, more preferably 20% to 90% by weight, even more preferably 30% to 80% by weight, and particularly preferably 40% to 70% by weight, in order to better exhibit the effects of the present invention.
[0090] The content of the polar group-containing monomer (b1) in the monomer component (M1) is preferably 1% to 50% by weight, more preferably 1% to 40% by weight, even more preferably 1% to 30% by weight, and particularly preferably 1% to 20% by weight, in order to better express the effects of the present invention.
[0091] In order to better express the effects of the present invention, the polar group-containing monomer (b1) preferably comprises at least one selected from the group consisting of a hydroxyl group-containing monomer (b1-1) and a monomer having a polar group other than a hydroxyl group (b1-2), and more preferably comprises both a hydroxyl group-containing monomer (b1-1) and a monomer having a polar group other than a hydroxyl group (b1-2).
[0092] The hydroxyl group-containing monomer (b1-1) may be one type or two or more types.
[0093] Examples of hydroxyl group-containing monomers (b1-1) include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polypropylene glycol mono(meth)acrylate; and N-hydroxyethyl (meth)acrylamide.
[0094] In order to better express the effects of the present invention, the hydroxyl group-containing monomer (b1-1) preferably has a glass transition temperature Tg of its homopolymer (homopolymer) of -60°C to -10°C, more preferably -55°C to -10°C, and even more preferably -45°C to -10°C. The glass transition temperature Tg of the homopolymer (homopolymer) of the hydroxyl group-containing monomer (b1-1) can affect the adhesive properties of the acrylic polymer (P1). By using a hydroxyl group-containing monomer (b1-1) that has a glass transition temperature Tg of its homopolymer (homopolymer) within the above range as the monomer component (M1), the effects of the present invention can be better expressed.
[0095] The glass transition temperature Tg of homopolymers of hydroxyl group-containing monomers (b1-1) can be determined by referring to the explanation for the glass transition temperature Tg of alkyl (meth)acrylates (a1).
[0096] In order to further express the effects of the present invention, the hydroxyl group-containing monomer (b1-1) is preferably a hydroxyalkyl (meth)acrylate, more preferably a hydroxyalkyl (meth)acrylate in which the alkyl group portion of the hydroxyalkyl group is a linear alkyl group having 2 to 4 carbon atoms, even more preferably 2-hydroxyethyl acrylate (HEA) (glass transition temperature Tg = -15°C of its homopolymer) and 4-hydroxybutyl acrylate (4HBA) (glass transition temperature Tg = -40°C of its homopolymer), and particularly preferably 4-hydroxybutyl acrylate (4HBA) (glass transition temperature Tg = -40°C of its homopolymer).
[0097] The content of hydroxyl group-containing monomer (b1-1) in polar group-containing monomer (b1) is preferably 10% to 100% by weight, more preferably 20% to 90% by weight, even more preferably 30% to 85% by weight, and particularly preferably 40% to 80% by weight, in order to better exhibit the effects of the present invention.
[0098] The content of the hydroxyl group-containing monomer (b1-1) in the monomer component (M1) is preferably 0% to 80% by weight, more preferably 10% to 70% by weight, even more preferably 20% to 60% by weight, and particularly preferably 30% to 50% by weight, in order to better express the effects of the present invention.
[0099] The monomers (b1-2) having polar groups other than hydroxyl groups may be one type or two or more types.
[0100] Examples of monomers having polar groups other than hydroxyl groups (b1-2) include N-vinyl-2-pyrrolidone, nitrogen-containing monomers other than N-vinyl-2-pyrrolidone, carboxyl group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, cyano group-containing monomers, acid anhydride group-containing monomers, vinyl esters (e.g., vinyl acetate (VAc), vinyl propionate, vinyl laurate), aromatic vinyl compounds, amide group-containing monomers, epoxy group-containing monomers, (meth)acryloylmorpholine, and vinyl ethers.
[0101] Examples of monomers containing a carboxyl group include acrylic acid (AA), methacrylic acid (MAA), carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0102] Examples of nitrogen-containing monomers other than N-vinyl-2-pyrrolidone include methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, (meth)acryloylmorpholine, N-vinyl carboxylic acid amides, and N-vinylcaprolactam; as well as cyano group-containing acrylic monomers such as acrylonitrile and methacrylonitrile.
[0103] In order to better express the effects of the present invention, the monomer (b1-2) having polar groups other than hydroxyl groups preferably has a glass transition temperature Tg of its homopolymer (homopolymer) of -30°C to 100°C, more preferably -20°C to 95°C, and even more preferably -10°C to 90°C. The glass transition temperature Tg of the homopolymer (homopolymer) of the monomer (b1-2) having polar groups other than hydroxyl groups may affect the adhesive properties of the acrylic polymer (P1). By using a monomer (b1-2) having polar groups other than hydroxyl groups that has a glass transition temperature Tg of its homopolymer (homopolymer) within the above range as the monomer (b1-2) that can be included in the monomer component (M1), the effects of the present invention can be better expressed.
[0104] As monomers having polar groups other than hydroxyl groups (b1-2), those that can better express the effects of the present invention are preferably monomers having polar groups other than hydroxyl groups whose homopolymers have a glass transition temperature Tg of 50°C to 100°C. The glass transition temperature Tg of the homopolymer of this monomer is preferably 60°C to 95°C, and more preferably 70°C to 90°C.
[0105] For the glass transition temperature Tg of homopolymers of monomers (b1-2) having polar groups other than hydroxyl groups, the explanation for the glass transition temperature Tg of homopolymers of alkyl (meth)acrylates (a1) that may be contained in the monomer component (M1) in section [A-1-2-1. Acrylic polymers (P1)] can be applied.
[0106] In order to further enhance the effects of the present invention, preferred monomers (b1-2) having polar groups other than hydroxyl groups include N-vinyl-2-pyrrolidone (the glass transition temperature Tg = 80°C of its homopolymer).
[0107] The content of monomers (b1-2) having polar groups other than hydroxyl groups in the polar group-containing monomer (b1) is preferably 0% to 90% by weight, more preferably 10% to 80% by weight, even more preferably 15% to 70% by weight, and particularly preferably 20% to 60% by weight, in order to better express the effects of the present invention.
[0108] The content of monomers (b1-2) having polar groups other than hydroxyl groups in monomer component (M1) is preferably 0% to 20% by weight, more preferably 0% to 10% by weight, even more preferably 0% to 9% by weight, and particularly preferably 0% to 8% by weight, in order to better express the effects of the present invention.
[0109] To further enhance the effects of the present invention, the monomer component (M1) preferably comprises an alkyl (meth)acrylate (a1) and at least one selected from the group consisting of a hydroxyl group-containing monomer (b1-1) and a monomer having a polar group other than a hydroxyl group (b1-2), more preferably comprising an alkyl (meth)acrylate (a1), a hydroxyl group-containing monomer (b1-1), and a monomer having a polar group other than a hydroxyl group (b1-2), and even more preferably a homopolymer thereof. The material comprises an alkyl (meth)acrylate (a1-1) having a glass transition temperature Tg in the range of -40°C to -10°C (preferably -35°C to -15°C, more preferably -30°C to -20°C), an alkyl (meth)acrylate (a1-2) whose homopolymer has a glass transition temperature Tg in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C), a hydroxyl group-containing monomer (b1-1), and a monomer (b1-2) having a polar group other than a hydroxyl group.
[0110] In order to further express the effects of the present invention, the total content ratio of alkyl (meth)acrylate (a1-1) in the monomer component (M1) having a glass transition temperature Tg of its homopolymer in the range of -40°C to -10°C (preferably -35°C to -15°C, more preferably -30°C to -20°C), alkyl (meth)acrylate (a1-2) having a glass transition temperature Tg of its homopolymer in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C), hydroxyl group-containing monomer (b1-1), and monomer (b1-2) having polar groups other than hydroxyl groups is preferably 60% to 100% by weight, more preferably 70% to 100% by weight, even more preferably 80% to 100% by weight, particularly preferably 90% to 100% by weight, and most preferably 95% to 100% by weight.
[0111] In order to further enhance the effects of the present invention, the monomer component (M1) preferably includes lauryl acrylate, 2-ethylhexyl acrylate, 4-hydroxybutyl acrylate, and N-vinyl-2-pyrrolidone.
[0112] The monomer component (M1) may include other monomers (c1) that do not fall under either alkyl (meth)acrylate (a1) or polar group-containing monomer (b1). The other monomers (c1) can be used, for example, to adjust the glass transition temperature (Tg) or tackiness of the acrylic polymer (P1). The other monomers may be one type or two or more types.
[0113] The content of other monomers (c1) in monomer component (M1) is preferably 20% by weight or less, more preferably 10% by weight or less, even more preferably 5% by weight or less, particularly preferably 3% by weight or less, and most preferably 1% by weight or less.
[0114] The photopolymerization initiator can be appropriately selected from any suitable photopolymerization initiator depending on the type of polymerization method. There may be only one type of photopolymerization initiator, or two or more types.
[0115] Examples of photopolymerization initiators include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, and acylphosphine oxide-based photopolymerization initiators.
[0116] Examples of benzoin ether-based photopolymerization initiators include, for example, benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one (a commercially available product is, for example, trade name "OMNIRAD651," manufactured by IGM Resins BV), and anisole methyl ether.
[0117] Examples of acetophenone-based photopolymerization initiators include, for example, 1-hydroxycyclohexylphenyl ketone (commercially available, for example, trade name "OMNIRAD184," manufactured by IGM Resins BV), 4-phenoxydichloroacetophenone, 4-t-butyl-dichloroacetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one (commercially available, for example, trade name "OMNIRAD2959," manufactured by IGM Resins BV), 2-hydroxy-2-methyl-1-phenyl-propan-1-one, and methoxyacetophenone.
[0118] Examples of α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)-phenyl]-2-hydroxy-2-methylpropan-1-one.
[0119] Examples of aromatic sulfonyl chloride-based photopolymerization initiators include, for example, 2-naphthalenesulfonyl chloride.
[0120] Examples of photoactive oxime-based photopolymerization initiators include, for example, 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime.
[0121] Examples of benzoin-based photopolymerization initiators include, for instance, benzoin.
[0122] Examples of benzyl-based photopolymerization initiators include, for example, benzyl.
[0123] Examples of benzophenone-based photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, and α-hydroxycyclohexylphenyl ketone.
[0124] Examples of ketal-based photopolymerization initiators include, for example, benzyldimethyl ketal.
[0125] Examples of thioxanthone-based photopolymerization initiators include, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0126] Examples of acylphosphine-based photopolymerization initiators include, specifically, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)(2,4,4-trimethylpentyl)phosphine oxide, bis(2,6-dimethoxybenzoyl)-n-butylphosphine oxide, bis(2,6-dimethoxybenzoyl)-(2-methylpropan-1-yl)phosphine oxide, bis(2,6-dimethoxybenzoyl)-(1-methylpropan-1-yl)phosphine oxide, and bis(2,6-dimethyl (Xybenzoyl)-t-butylphosphine oxide, bis(2,6-dimethoxybenzoyl)cyclohexylphosphine oxide, bis(2,6-dimethoxybenzoyl)octylphosphine oxide, bis(2-methoxybenzoyl)(2-methylpropan-1-yl)phosphine oxide, bis(2-methoxybenzoyl)(1-methylpropan-1-yl)phosphine oxide, bis(2,6-diethoxybenzoyl)(2-methylpropan-1-yl)phosphine oxide, bis(2,6-diethoxybenzoyl)(1-methylprop Pan-1-yl)phosphine oxide, bis(2,6-dibutoxybenzoyl)(2-methylpropan-1-yl)phosphine oxide, bis(2,4-dimethoxybenzoyl)(2-methylpropan-1-yl)phosphine oxide, bis(2,4,6-trimethylbenzoyl)(2,4-dipentoxyphenyl)phosphine oxide, bis(2,6-dimethoxybenzoyl)benzylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylpropylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2 - Phenylethylphosphine oxide, bis(2,6-dimethoxybenzoyl)benzylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylpropylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylethylphosphine oxide, 2,6-dimethoxybenzoylbenzylbutylphosphine oxide, 2,6-dimethoxybenzoylbenzyloctylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,5-diisopropylphenylphosphine oxide, bis(2,4,6-Trimethylbenzoyl)-2-methylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-4-methylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,5-diethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,3,5,6-tetramethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl) Examples include -2,4,4-trimethylpentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)isobutylphosphine oxide, 2,6-dimethitoxybenzoyl-2,4,6-trimethylbenzoyl-n-butylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-dibutoxyphenylphosphine oxide, 1,10-bis[bis(2,4,6-trimethylbenzoyl)phosphine oxide]decane, and tri(2-methylbenzoyl)phosphine oxide.
[0127] The amount of photopolymerization initiator used can be set to any appropriate amount as long as it does not impair the effects of the present invention. The amount of photopolymerization initiator used is preferably 0.001 to 10 parts by weight, more preferably 0.005 to 5 parts by weight, even more preferably 0.007 to 3 parts by weight, and particularly preferably 0.01 to 1 part by weight, per 100 parts by weight of monomer component (M1), in order to better express the effects of the present invention.
[0128] [A-1-2-2. Acrylic polymer (P2)] One embodiment of the acrylic polymer is an acrylic polymer (P2) prepared by solution polymerization using a thermal polymerization initiator. As for the polymerization method using the thermal polymerization initiator, any suitable method can be used, such as conventionally known methods, as long as it does not impair the effects of the present invention.
[0129] The acrylic polymer (P2) is obtained by polymerizing the monomer component (M2). The monomer component (M2) referred to here does not include the crosslinking agent that may be included in the acrylic adhesive composition, as described later. When obtaining the acrylic polymer (P2) by polymerization, in addition to the monomer component (M2) and the thermal polymerization initiator, any suitable additive may be used as long as it does not impair the effects of the present invention.
[0130] Acrylic polymers (P2) can thus be defined as those obtained by polymerizing monomer components (M2). This is because acrylic polymers (P2) are formed when monomer components (M2) undergo a polymerization reaction, and it is impossible and impractical to directly identify acrylic polymers (P2) by their structure. Therefore, the definition "obtained by polymerizing monomer components (M2)" appropriately identifies acrylic polymers (P2) as a "substance."
[0131] The acrylic polymer (P2) preferably has a Tg of -70°C to 50°C, more preferably -60°C to 40°C, even more preferably -55°C to 30°C, and particularly preferably -50°C to 20°C, in order to better exhibit the effects of the present invention. By adjusting the Tg of the acrylic polymer (P2) to the above specific range, the effects of the present invention can be better exhibited.
[0132] The Tg of an acrylic polymer (P2) refers to the value obtained from Fox's formula, based on the Tg of the homopolymer of each monomer constituting the acrylic polymer (P2) and the weight fraction (weight-based copolymerization ratio) of said monomer. For Fox's formula and the Tg of various homopolymers, refer to the explanation in section [A-1-2-1. Acrylic Polymer (P1)].
[0133] The monomer component (M2) preferably comprises an alkyl (meth)acrylate (a2) and a polar group-containing monomer (b2). The alkyl (meth)acrylate (a2) may consist of only one type or two or more types. The polar group-containing monomer (b2) may consist of only one type or two or more types.
[0134] The alkyl group in the ester portion of alkyl(meth)acrylate (a2) (hereinafter sometimes referred to as "alkyl group in the ester portion") does not include alkyl groups containing hydroxyl groups or alkyl groups containing polar groups other than hydroxyl groups. Therefore, alkyl(meth)acrylate (a2) is clearly distinguished from polar group-containing monomer (b2).
[0135] The content of alkyl (meth)acrylate (a2) in the monomer component (M2) is preferably 40% to 99% by weight, more preferably 45% to 90% by weight, even more preferably 50% to 80% by weight, and particularly preferably 60% to 75% by weight, in order to better express the effects of the present invention.
[0136] The alkyl group of the ester portion is preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 18 carbon atoms, even more preferably an alkyl group having 1 to 16 carbon atoms, and particularly preferably an alkyl group having 1 to 14 carbon atoms, in order to better express the effects of the present invention.
[0137] The alkyl group in the ester portion is preferably a linear alkyl group, as this allows for better expression of the effects of the present invention. Here, "linear" includes both linear and branched alkyl groups.
[0138] For alkyl(meth)acrylates (a2) in which the alkyl group of the ester portion is a chain-like alkyl group having 1 to 20 carbon atoms, the explanation for alkyl(meth)acrylates (a1) in which the alkyl group of the ester portion is a chain-like alkyl group having 1 to 20 carbon atoms in section [A-1-2-1. Acrylic polymers (P1)] can be applied.
[0139] In order to better express the effects of the present invention, the alkyl (meth)acrylate (a2) that may be included in the monomer component (M2) preferably includes alkyl (meth)acrylate (a2-1) whose homopolymer (homopolymer) has a glass transition temperature Tg in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C). The effects of the present invention can be better expressed by including alkyl (meth)acrylate (a2-1) in alkyl (meth)acrylate (M2).
[0140] Examples of alkyl (meth)acrylate (a2-1) include 2-ethylhexyl acrylate (2EHA) (the glass transition temperature Tg = -70°C of its homopolymer).
[0141] The content ratio of alkyl (meth)acrylate (a2-1) in the total amount of alkyl (meth)acrylate (a2) that can be contained in the monomer component (M2) is preferably 30% to 100% by weight, more preferably 40% to 100% by weight, even more preferably 50% to 100% by weight, and particularly preferably 60% to 100% by weight, in order to better exhibit the effects of the present invention.
[0142] The content of alkyl (meth)acrylate (a2-1) in the total amount of monomer component (M2) is preferably 50% to 100% by weight, more preferably 60% to 100% by weight, even more preferably 70% to 100% by weight, and particularly preferably 80% to 100% by weight, in order to better exhibit the effects of the present invention.
[0143] In order to better express the effects of the present invention, the alkyl (meth)acrylate (a2) that may be included in the monomer component (M2) preferably includes alkyl (meth)acrylate (a2-2) whose homopolymer (homopolymer) has a glass transition temperature Tg in the range of 90°C to 120°C (preferably 95°C to 115°C, more preferably 100°C to 110°C). The effects of the present invention can be better expressed by including alkyl (meth)acrylate (a2-2) in alkyl (meth)acrylate (M2).
[0144] Examples of alkyl (meth)acrylate (a2-2) include methyl methacrylate (MMA) (whose homopolymer has a glass transition temperature Tg = 105°C).
[0145] The content ratio of alkyl (meth)acrylate (a2-2) in the total amount of alkyl (meth)acrylate (a2) that can be contained in the monomer component (M2) is preferably 60% to 100% by weight, more preferably 70% to 100% by weight, even more preferably 80% to 100% by weight, and particularly preferably 90% to 100% by weight, in order to better exhibit the effects of the present invention.
[0146] The content of alkyl (meth)acrylate (a2-2) in the total amount of monomer component (M2) is preferably 0% to 40% by weight, more preferably 0% to 30% by weight, even more preferably 0% to 20% by weight, and particularly preferably 0% to 15% by weight, in order to better express the effects of the present invention.
[0147] The content of the polar group-containing monomer (b2) in the monomer component (M2) is preferably 0% to 45% by weight, more preferably 0% to 40% by weight, even more preferably 0% to 35% by weight, and particularly preferably 0% to 30% by weight, in order to better express the effects of the present invention.
[0148] In order to better express the effects of the present invention, the polar group-containing monomer (b2) preferably comprises at least one selected from the group consisting of a hydroxyl group-containing monomer (b2-1) and a monomer having a polar group other than a hydroxyl group (b2-2), and more preferably comprises both a hydroxyl group-containing monomer (b2-1) and a monomer having a polar group other than a hydroxyl group (b2-2).
[0149] The hydroxyl group-containing monomer (b2-1) may be one type or two or more types.
[0150] For hydroxyl group-containing monomers (b2-1), the explanation for hydroxyl group-containing monomers (b1-1) in section [A-1-2-1. Acrylic polymers (P1)] can be applied.
[0151] In order to better express the effects of the present invention, the hydroxyl group-containing monomer (b2-1) preferably has a glass transition temperature Tg of its homopolymer (homopolymer) of -60°C to -10°C, more preferably -55°C to -10°C, and even more preferably -45°C to -10°C. The glass transition temperature Tg of the homopolymer (homopolymer) of the hydroxyl group-containing monomer (b2-1) can affect the adhesive properties of the acrylic polymer (P2). By using a hydroxyl group-containing monomer (b2-1) that can be included in the monomer component (M2) and whose homopolymer (homopolymer) has a glass transition temperature Tg within the above range, the effects of the present invention can be better expressed.
[0152] For the glass transition temperature Tg of homopolymers of hydroxyl group-containing monomers (b2-1), the explanation for the glass transition temperature Tg of homopolymers of alkyl (meth)acrylates (a1) that may be contained in the monomer component (M1) in section [A-1-2-1. Acrylic polymers (P1)] can be applied.
[0153] In order to further express the effects of the present invention, the hydroxyl group-containing monomer (b2-1) is preferably a hydroxyalkyl (meth)acrylate, more preferably a hydroxyalkyl (meth)acrylate in which the alkyl group portion of the hydroxyalkyl group is a linear alkyl group having 2 to 4 carbon atoms, even more preferably 2-hydroxyethyl acrylate (HEA) (glass transition temperature Tg = -15°C of its homopolymer) and 4-hydroxybutyl acrylate (4HBA) (glass transition temperature Tg = -40°C of its homopolymer), and particularly preferably 2-hydroxyethyl acrylate (HEA) (glass transition temperature Tg = -15°C of its homopolymer).
[0154] The content ratio of hydroxyl group-containing monomer (b2-1) in polar group-containing monomer (b2) is preferably 10% to 100% by weight, more preferably 20% to 100% by weight, even more preferably 30% to 100% by weight, and particularly preferably 40% to 100% by weight, in order to better exhibit the effects of the present invention.
[0155] The content of the hydroxyl group-containing monomer (b2-1) in the monomer component (M2) is preferably 0% to 45% by weight, more preferably 0% to 30% by weight, even more preferably 0% to 25% by weight, and particularly preferably 0% to 20% by weight, in order to better express the effects of the present invention.
[0156] The monomer (b2-2) having a polar group other than a hydroxyl group may be one type or two or more types.
[0157] For monomers having polar groups other than hydroxyl groups (b2-2), the explanation for monomers having polar groups other than hydroxyl groups (b1-2) in section [A-1-2-1. Acrylic polymers (P1)] may be applied.
[0158] In order to better express the effects of the present invention, the monomer (b2-2) having polar groups other than hydroxyl groups preferably has a glass transition temperature Tg of its homopolymer (homopolymer) of -30°C to 100°C, more preferably -20°C to 95°C, and even more preferably -10°C to 90°C. The glass transition temperature Tg of the homopolymer (homopolymer) of the monomer (b2-2) having polar groups other than hydroxyl groups may affect the adhesive properties of the acrylic polymer (P2). By using a monomer (b2-2) having polar groups other than hydroxyl groups that has a glass transition temperature Tg of its homopolymer (homopolymer) within the above range as the monomer (b2-2) that can be included in the monomer component (M2), the effects of the present invention can be better expressed.
[0159] As monomers having polar groups other than hydroxyl groups (b2-2), those that can better express the effects of the present invention are preferably monomers having polar groups other than hydroxyl groups whose homopolymer has a glass transition temperature Tg of 50°C to 100°C. The glass transition temperature Tg of the homopolymer of this monomer is preferably 60°C to 95°C, and more preferably 70°C to 90°C.
[0160] For the glass transition temperature Tg of homopolymers of monomers (b2-2) having polar groups other than hydroxyl groups, the explanation for the glass transition temperature Tg of homopolymers of alkyl (meth)acrylates (a1) that may be contained in the monomer component (M1) in section [A-1-2-1. Acrylic polymers (P1)] can be applied.
[0161] In order to further enhance the effects of the present invention, a preferred monomer (b2-2) having a polar group other than a hydroxyl group is N-vinyl-2-pyrrolidone (the glass transition temperature Tg = 80°C of its homopolymer).
[0162] The content of monomers (b2-2) having polar groups other than hydroxyl groups in the polar group-containing monomer (b2) is preferably 0% to 90% by weight, more preferably 10% to 80% by weight, even more preferably 20% to 70% by weight, and particularly preferably 30% to 60% by weight, in order to better express the effects of the present invention.
[0163] The content of monomers (b2-2) having polar groups other than hydroxyl groups in monomer component (M2) is preferably 0% to 35% by weight, more preferably 0% to 30% by weight, even more preferably 0% to 25% by weight, and particularly preferably 0% to 20% by weight, in order to better express the effects of the present invention.
[0164] To further enhance the effects of the present invention, the monomer component (M2) preferably comprises an alkyl (meth)acrylate (a2) and at least one selected from the group consisting of a hydroxyl group-containing monomer (b2-1) and a monomer having a polar group other than a hydroxyl group (b2-2), more preferably comprising an alkyl (meth)acrylate (a2), a hydroxyl group-containing monomer (b2-1), and a monomer having a polar group other than a hydroxyl group (b2-2), and even more preferably a glass homopolymer thereof. The material comprises an alkyl (meth)acrylate (a2-1) having a transition temperature Tg in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C), an alkyl (meth)acrylate (a2-2) whose homopolymer has a glass transition temperature Tg in the range of -120°C to -90°C (preferably -115°C to -95°C, more preferably -110°C to -100°C), a hydroxyl group-containing monomer (b2-1), and a monomer having a polar group other than a hydroxyl group (b2-2).
[0165] In order to further express the effects of the present invention, the total content ratio of alkyl (meth)acrylate (a2-1) in the monomer component (M2) having a glass transition temperature Tg of its homopolymer in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C), alkyl (meth)acrylate (a2-2) having a glass transition temperature Tg of its homopolymer in the range of -120°C to -90°C (preferably -115°C to -95°C, more preferably -110°C to -100°C), hydroxyl group-containing monomer (b2-1), and monomer (b2-2) having polar groups other than hydroxyl groups is preferably 60% to 100% by weight, more preferably 70% to 100% by weight, even more preferably 80% to 100% by weight, particularly preferably 90% to 100% by weight, and most preferably 95% to 100% by weight.
[0166] In order to further enhance the effects of the present invention, the monomer component (M1) preferably includes 2-ethylhexyl acrylate, methyl methacrylate, 2-hydroxyethyl acrylate, and N-vinyl-2-pyrrolidone.
[0167] The monomer component (M2) may include other monomers (c2) that do not fall under either alkyl (meth)acrylate (a2) or polar group-containing monomers (b2). The other monomers (c2) can be used, for example, to adjust the glass transition temperature (Tg) of the acrylic polymer (P1), adjust the tackiness, etc. The other monomers may be one type or two or more types.
[0168] The content of other monomers (c2) in monomer component (M1) is preferably 20% by weight or less, more preferably 10% by weight or less, even more preferably 5% by weight or less, particularly preferably 3% by weight or less, and most preferably 1% by weight or less.
[0169] The thermal polymerization initiator can be appropriately selected from any suitable thermal polymerization initiator depending on the type of polymerization method. There may be only one thermal polymerization initiator or two or more.
[0170] Examples of thermal polymerization initiators include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionic acid)dimethyl, 4,4'-azobis-4-cyanovaleric acid, azobisisovaleronitrile, 2,2'-azobis(2-amidinopropane)dihydrochloride, and 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]di Azo initiators such as hydrochlorides, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(N,N'-dimethylene isobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (VA-057, manufactured by Wako Pure Chemical Industries, Ltd.); persulfates such as potassium persulfate and ammonium persulfate, di(2-ethylhexyl) peroxydicarbonate, di Examples include peroxide initiators such as (4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, t-butylperoxyneodecanoate, t-hexylperoxypivalate, t-butylperoxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, t-butylperoxyisobutyrate, 1,1-di(t-hexylperoxy)cyclohexane, t-butylhydroperoxide, and hydrogen peroxide; redox initiators combining peroxides with reducing agents, such as combinations of persulfates and sodium bisulfite, or combinations of peroxides and sodium ascorbate; substituted ethane initiators such as phenyl-substituted ethane; and aromatic carbonyl compounds.
[0171] The amount of thermal polymerization initiator used can be set to any appropriate amount as long as it does not impair the effects of the present invention. The amount of thermal polymerization initiator used is preferably 0.001 to 10 parts by weight, more preferably 0.005 to 5 parts by weight, even more preferably 0.007 to 3 parts by weight, and particularly preferably 0.01 to 1 part by weight, per 100 parts by weight of monomer component (M2), in order to better express the effects of the present invention.
[0172] [A-1-2-3. First embodiment of acrylic adhesive (photocurable acrylic adhesive)] The first embodiment of the acrylic adhesive is a photocurable acrylic adhesive, which is typically formed by a photocuring reaction of a photocurable acrylic adhesive composition containing an acrylic polymer (P1).
[0173] The photocurable acrylic adhesive is formed from a photocurable acrylic adhesive composition by any suitable method. Typical such formation methods include applying the photocurable acrylic adhesive composition onto any suitable substrate, then placing another suitable substrate on the surface of the applied adhesive layer, and curing it by ultraviolet irradiation. Any suitable application method can be used for applying the photocurable acrylic adhesive composition, as long as it does not impair the effects of the present invention. Examples of such application methods include the roll coating method, gravure roll coating method, reverse roll coating method, kiss roll coating method, dip roll coating method, bar coating method, roll brush coating method, spray coating method, knife coating method, air knife coating method, comma coating method, direct coating method, and die coating method.
[0174] Heating may be performed as needed during the formation of the photocurable acrylic adhesive. Furthermore, aging may be performed for purposes such as adjusting component migration within the formed photocurable acrylic adhesive, promoting the crosslinking reaction, and alleviating any strain that may exist within the photocurable acrylic adhesive.
[0175] The photocurable acrylic adhesive composition may contain alkyl (meth)acrylate (a1-2). The type of alkyl (meth)acrylate (a1-2) may be the same as or different from the type of alkyl (meth)acrylate (a1-2) that can be used to produce the acrylic polymer (P1).
[0176] The content of alkyl (meth)acrylate (a1-2) in the photocurable acrylic adhesive composition is preferably 20% to 90% by weight, more preferably 30% to 80% by weight, even more preferably 40% to 70% by weight, and particularly preferably 50% to 65% by weight, relative to the total amount (100% by weight) of the acrylic polymer (P1), in order to better exhibit the effects of the present invention.
[0177] The photocurable acrylic adhesive composition preferably contains a crosslinking agent (L1). The crosslinking agent (L1) may be one type or two or more types.
[0178] The amount of crosslinking agent (L1) in the photocurable acrylic adhesive composition can be set to any appropriate amount as long as it does not impair the effects of the present invention. The amount of crosslinking agent (L1) in the photocurable acrylic adhesive composition is preferably 0.001 to 0.5 parts by weight, more preferably 0.005 to 0.3 parts by weight, even more preferably 0.01 to 0.2 parts by weight, and particularly preferably 0.05 to 0.1 parts by weight, per 100 parts by weight of acrylic polymer (P1), in order to better express the effects of the present invention.
[0179] As the crosslinking agent (L1), any suitable crosslinking agent can be used as long as it does not impair the effects of the present invention. Preferably, such a crosslinking agent (L1) is a polyfunctional (meth)acrylate.
[0180] As the polyfunctional (meth)acrylate, any suitable polyfunctional (meth)acrylate can be used as long as it does not impair the effects of the present invention. There may be only one type of polyfunctional (meth)acrylate, or there may be two or more types. Specifically, such polyfunctional (meth)acrylates include, for example, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6- Examples include ester compounds of polyhydric alcohols such as hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate with (meth)acrylic acid; allyl(meth)acrylate; vinyl(meth)acrylate; divinylbenzene; epoxy acrylate; polyester acrylate; urethane acrylate; butyl di(meth)acrylate; and hexyl di(meth)acrylate.
[0181] The light-curing acrylic adhesive composition may contain an acrylic oligomer. The acrylic oligomer may be one type or two or more types.
[0182] The content of acrylic oligomers in the photocurable acrylic adhesive composition can be set to any appropriate content as long as it does not impair the effects of the present invention. The content of acrylic oligomers in the photocurable acrylic adhesive composition is preferably 0.1 to 20 parts by weight, more preferably 1 to 15 parts by weight, even more preferably 3 to 10 parts by weight, and particularly preferably 5 to 8 parts by weight, per 100 parts by weight of acrylic polymer (P1), in order to better express the effects of the present invention.
[0183] The weight-average molecular weight of the acrylic oligomer is preferably 1,000 to 30,000, more preferably 1,000 to 20,000, even more preferably 1,500 to 10,000, and particularly preferably 2,000 to 8,000. The effects of the present invention can be more fully realized when the photocurable acrylic adhesive composition contains an acrylic oligomer.
[0184] The weight-average molecular weight (Mw) can be determined by converting it to polystyrene equivalent using the GPC method. For example, it can be measured using the high-speed GPC instrument "HPLC-8120GPC" manufactured by Tosoh Corporation under the following conditions. Column: TSKgel SuperHZM-H / HZ4000 / HZ3000 / HZ2000 Solvent: tetrahydrofuran Flow rate: 0.6ml / min
[0185] The glass transition temperature (Tg) of the acrylic oligomer is preferably 20°C to 300°C, more preferably 30°C to 300°C, and more preferably 40°C to 300°C.
[0186] The Tg of an acrylic oligomer refers to the value obtained from Fox's formula, based on the Tg of the homopolymer of each monomer constituting the acrylic oligomer and the weight fraction (weight-based copolymerization ratio) of the monomer. For Fox's formula and the Tg of various homopolymers, refer to the explanation in section [A-1-2-1. Acrylic Polymers (P1)].
[0187] As acrylic oligomers, those obtained from monomer compositions containing a (meth)acrylic acid ester having a cyclic structure within the molecule are preferred, and those obtained from monomer compositions containing a (meth)acrylic acid alkyl ester having a cyclic structure within the molecule and a linear or branched alkyl group are more preferred.
[0188] The (meth)acrylic acid ester having a cyclic structure within the molecule may be one type or two or more types.
[0189] The alkyl (meth)acrylate having a linear or branched alkyl group may be one type or two or more types.
[0190] In (meth)acrylic acid esters having a cyclic structure within the molecule, the cyclic structure may be either an aromatic ring or a non-aromatic ring.
[0191] Examples of aromatic rings include aromatic carbon rings (such as monocyclic carbon rings like benzene rings, and fused carbon rings like naphthalene rings), and various aromatic heterocycles.
[0192] Examples of non-aromatic rings include non-aromatic aliphatic rings (non-aromatic alicyclic rings) (e.g., cycloalkane rings such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane rings; cycloalkene rings such as cyclohexene rings), non-aromatic bridged rings (e.g., bicyclic hydrocarbon rings in pinane, pinene, bornane, norbornane, norbornene; aliphatic hydrocarbon rings with three or more rings (bridged hydrocarbon rings) in adamantane, etc.), and non-aromatic heterocycles (e.g., epoxy rings, oxolane rings, oxetane rings). Examples of aliphatic hydrocarbon rings with three or more rings (bridged hydrocarbon rings with three or more rings) include dicyclopentanyl group, dicyclopentenyl group, adamantyl group, tricyclopentanyl group, and tricyclopentenyl group.
[0193] Examples of (meth)acrylic acid esters having a cyclic structure within the molecule include, for example, cycloalkyl (meth)acrylic acid esters such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate; (meth)acrylic acid esters having a bicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1- Examples include (meth)acrylic acid esters having three or more aliphatic hydrocarbon rings, such as adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate; and (meth)acrylic acid esters having aromatic rings, such as aryl (meth)acrylates like phenyl (meth)acrylate, aryloxyalkyl (meth)acrylates like phenoxyethyl (meth)acrylate, and arylalkyl (meth)acrylates like benzyl (meth)acrylate.
[0194] As (meth)acrylic acid esters having a cyclic structure within the molecule, non-aromatic ring-containing (meth)acrylic acid esters are preferred in terms of being able to better express the effects of the present invention, more preferably cyclohexyl acrylate (CHA), cyclohexyl methacrylate (CHMA), dicyclopentanyl acrylate (DCPA), and dicyclopentanyl methacrylate (DCPMA), and even more preferably dicyclopentanyl acrylate (DCPA) and dicyclopentanyl methacrylate (DCPMA).
[0195] The content of (meth)acrylic acid esters having a cyclic structure within the molecule in all monomers that can be used to constitute the acrylic oligomer is preferably 10 to 90 parts by weight, and more preferably 20 to 80 parts by weight, per 100 parts by weight of all monomers, in order to better express the effects of the present invention.
[0196] Examples of alkyl (meth)acrylate esters having linear or branched alkyl groups include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and methacrylic acid Examples include alkyl esters of (meth)acrylates having 1 to 20 carbon atoms in the alkyl group, such as isooctyl, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, methyl methacrylate (MMA) is preferred in that it can better exhibit the effects of the present invention.
[0197] The content of alkyl (meth)acrylate having a linear or branched alkyl group in the total monomers that can be used to constitute the acrylic oligomer is preferably 10 to 90 parts by weight, more preferably 20 to 80 parts by weight, and even more preferably 20 to 60 parts by weight, per 100 parts by weight of the total monomer, in order to better express the effects of the present invention.
[0198] The total monomers (monomer composition) that can be used to constitute the acrylic oligomer may include, in addition to (meth)acrylic acid esters having a cyclic structure in the molecule and (meth)acrylic acid alkyl esters having linear or branched alkyl groups, other monomers (copolymerizable monomers) that can copolymerize with these monomers. The content of other monomers (copolymerizable monomers) in the total monomers (monomer composition) that can be used to constitute the acrylic oligomer is preferably less than 50 parts by weight, more preferably 40 parts by weight or less, even more preferably 30 parts by weight or less, and particularly preferably 20 parts by weight or less, per 100 parts by weight of the total monomer.
[0199] Other monomers (copolymerizable monomers) include, for example, alkoxyalkyl esters of (meth)acrylates (e.g., 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 4-ethoxybutyl (meth)acrylate, etc.), carboxyl group-containing monomers (e.g., acid anhydride group-containing monomers such as (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, maleic anhydride, etc.), hydroxyl group-containing monomers (e.g., hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, etc.); vinyl alcohol; allyl alcohol; etc. Examples include monomers containing amide groups (e.g., (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, etc.), monomers containing amino groups (e.g., aminoethyl(meth)acrylate, dimethylaminoethyl(meth)acrylate, t-butylaminoethyl(meth)acrylate, etc.), monomers containing cyano groups (e.g., acrylonitrile, methacrylonitrile, etc.), monomers containing sulfonic acid groups (e.g., sodium vinylsulfonate, etc.), monomers containing phosphate groups (e.g., 2-hydroxyethylacryloylphosphate, etc.), monomers containing isocyanate groups (e.g., 2-methacryloyloxyethyl isocyanate, etc.), and monomers containing imide groups (e.g., cyclohexylmaleimide, isopropylmaleimide, etc.).
[0200] The total monomers (monomer composition) that can be used to constitute the acrylic oligomer particularly preferably include (1) at least one monomer selected from dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate, and (2) methyl methacrylate. In this case, the content of monomer (1) is preferably 30 to 70 parts by weight and the content of monomer (2) is preferably 30 to 70 parts by weight per 100 parts by weight of the total monomers (monomer composition) that can be used to constitute the acrylic oligomer.
[0201] Acrylic oligomers can be produced by any suitable polymerization method, provided that the effects of the present invention are not impaired. Examples of such polymerization methods include solution polymerization, emulsion polymerization, bulk polymerization, and polymerization by active energy ray irradiation (active energy ray polymerization). Among these, bulk polymerization and solution polymerization are preferred, and solution polymerization is more preferred.
[0202] Examples of solvents that can be used in polymerization include organic solvents such as esters like ethyl acetate and n-butyl acetate; aromatic hydrocarbons like toluene and benzene; aliphatic hydrocarbons like n-hexane and n-heptane; alicyclic hydrocarbons like cyclohexane and methylcyclohexane; and ketones like methyl ethyl ketone and methyl isobutyl ketone. One solvent may be used, or two or more solvents may be used.
[0203] In polymerization, any suitable polymerization initiator (e.g., a thermal polymerization initiator or a photopolymerization initiator) can be used, as long as it does not impair the effects of the present invention. One polymerization initiator may be used, or two or more may be used. When performing solution polymerization, it is preferable to use an oil-soluble polymerization initiator.
[0204] As a thermal polymerization initiator, any suitable thermal polymerization initiator can be used as long as it does not impair the effects of the present invention. There may be only one thermal polymerization initiator or two or more. For specific examples of such thermal polymerization initiators, refer to the explanation of thermal polymerization initiators in section [A-1-2-2. Acrylic Polymers (P2)].
[0205] The content of the thermal polymerization initiator is preferably 0.1 to 15 parts by weight per 100 parts by weight of the total monomer (monomer composition) that can be used to constitute the acrylic oligomer.
[0206] As the photopolymerization initiator, any suitable photopolymerization initiator can be used as long as it does not impair the effects of the present invention. There may be only one type of photopolymerization initiator or two or more types. For specific examples of such photopolymerization initiators, refer to the explanation of photopolymerization initiators in section [A-1-2-1. Acrylic Polymers (P1)].
[0207] The photopolymerization initiator content is preferably 0.001 to 0.5 parts by weight per 100 parts by weight of the total monomer (monomer composition) that can be used to constitute the acrylic oligomer.
[0208] In polymerization of acrylic oligomers, a chain transfer agent may be used to adjust the molecular weight (preferably to adjust the weight-average molecular weight to 1,000 to 30,000). Examples of chain transfer agents include 2-mercaptoethanol, α-thioglycerol, 2,3-dimercapto-1-propanol, octyl mercaptan, t-nonyl mercaptan, dodecyl mercaptan (lauryl mercaptan), t-dodecyl mercaptan, glycidyl mercaptan, thioglycolic acid, methyl thioglycolate, ethyl thioglycolate, propyl thioglycolate, butyl thioglycolate, t-butyl thioglycolate, 2-ethylhexyl thioglycolate, octyl thioglycolate, isooctyl thioglycolate, decyl thioglycolate, dodecyl thioglycolate, thioglycolic acid ester of ethylene glycol, thioglycolic acid ester of neopentyl glycol, thioglycolic acid ester of pentaerythritol, and α-methylstyrene dimer. Among these, α-thioglycerol and methyl thioglycolate are preferred, and α-thioglycerol is particularly preferred, from the viewpoint of suppressing whitening of the double-sided adhesive tape of the present invention. The chain transfer agent may be one type or two or more types.
[0209] The content of the chain transfer agent is preferably 0.1 to 20 parts by weight, more preferably 0.2 to 15 parts by weight, and even more preferably 0.3 to 10 parts by weight, per 100 parts by weight of the total monomer (monomer composition) that can be used to constitute the acrylic oligomer.
[0210] The photocurable acrylic adhesive composition may contain any other suitable components as long as they do not impair the effects of the present invention. Examples of such other components include tackifiers, inorganic fillers, organic fillers, metal powders, pigments, colorants, foils, softeners, anti-aging agents, conductive agents, UV absorbers, antioxidants, light stabilizers, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, other crosslinking agents, solvents, catalysts, crosslinking catalysts, and crosslinking retarders.
[0211] [A-1-2-4. Second embodiment of acrylic adhesive (thermosetting acrylic adhesive)] A second embodiment of the acrylic adhesive is a thermosetting acrylic adhesive, which is typically formed by a crosslinking reaction of a thermosetting acrylic adhesive composition containing an acrylic polymer (P2).
[0212] The thermosetting acrylic adhesive is formed from a thermosetting acrylic adhesive composition by any suitable method. Typical such formation methods include applying the thermosetting acrylic adhesive composition onto any suitable substrate, heating and drying as necessary, and curing as necessary to form a sheet of thermosetting acrylic adhesive on the substrate. Any application method can be used as long as it does not impair the effects of the present invention. Examples of such application methods include the roll coating method, gravure roll coating method, reverse roll coating method, kiss roll coating method, dip roll coating method, bar coating method, roll brush coating method, spray coating method, knife coating method, air knife coating method, comma coating method, direct coating method, and die coating method.
[0213] The heating and drying of the thermosetting acrylic adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. For example, heating to a temperature of about 60°C to 180°C is one such heating and drying method. The curing of the acrylic adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. For example, curing methods include ultraviolet irradiation, laser irradiation, alpha-ray irradiation, beta-ray irradiation, gamma-ray irradiation, X-ray irradiation, and electron beam irradiation.
[0214] When forming a thermosetting acrylic adhesive, aging may be performed as needed to adjust component migration within the formed thermosetting acrylic adhesive, promote crosslinking reactions, and alleviate any strain that may exist within the photocurable acrylic adhesive.
[0215] The thermosetting acrylic adhesive composition preferably contains a crosslinking agent (L2). The crosslinking agent (L2) may be one type or two or more types.
[0216] The use of a crosslinking agent (L2) can impart appropriate cohesive force to a thermosetting acrylic adhesive. The crosslinking agent (L2) can be included in the thermosetting acrylic adhesive in the form after the crosslinking reaction, in the form before the crosslinking reaction, in a partially crosslinked form, or in intermediate or composite forms therein. Typically, the crosslinking agent (L2) is included in the thermosetting acrylic adhesive in the form after the crosslinking reaction.
[0217] The proportion of the crosslinking agent (L2) in the thermosetting acrylic adhesive composition is preferably 0.005 to 10 parts by weight, more preferably 0.01 to 5 parts by weight, even more preferably 0.01 to 3 parts by weight, even more preferably 0.01 to 2 parts by weight, particularly preferably 0.01 to 1.5 parts by weight, and most preferably 0.01 to 1.3 parts by weight, per 100 parts by weight of the acrylic polymer (P2), in order to better express the effects of the present invention.
[0218] Examples of crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, silicone-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, silane-based crosslinking agents, alkyl etherified melamine-based crosslinking agents, metal chelate-based crosslinking agents, and peroxides. In terms of being able to better express the effects of the present invention, isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and peroxides are preferred, and isocyanate-based crosslinking agents and peroxides are more preferred.
[0219] Isocyanate-based crosslinking agents can be compounds having two or more isocyanate groups (including isocyanate-regenerating polar groups in which isocyanate groups are temporarily protected by a blocking agent or quantification, etc.) in one molecule. Examples of isocyanate-based crosslinking agents include aromatic isocyanates such as tolylene diisocyanate and xylene diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; and aliphatic isocyanates such as hexamethylene diisocyanate.
[0220] Examples of isocyanate-based crosslinking agents include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic diisocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate, and polymethylene polyphenyl isocyanate; trimethylolpropane / tolylene diisocyanate trimer adduct (e.g., manufactured by Tosoh Corporation, trade name: Coronate L), trimethylolpropane / hexamethylene diisocyanate trimer adduct (e.g., manufactured by Tosoh Corporation, trade name: Coronate HL), and isocyanurate derivatives of hexamethylene diisocyanate (e.g., manufactured by Tosoh Corporation, Examples include isocyanate adducts such as Coronate HX; trimethylolpropane adducts of xylylene diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D110N), trimethylolpropane adducts of xylylene diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D120N), trimethylolpropane adducts of isophorone diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D140N), trimethylolpropane adducts of hexamethylene diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D160N); polyether polyisocyanates, polyester polyisocyanates, and adducts thereof with various polyols; and polyfunctionalized polyisocyanates with isocyanurate bonds, biuret bonds, allophanate bonds, etc. Among these, aromatic isocyanates and alicyclic isocyanates are preferred because they can achieve a good balance between deformability and cohesiveness.
[0221] As epoxy crosslinking agents, polyfunctional epoxy compounds having two or more epoxy groups in one molecule can be used. Examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylenediline, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and sorbitol polyglycidyl ether. Examples of epoxy crosslinking agents include tel, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate ester, diglycidyl o-phthalate ester, triglycidyl-tris(2-hydroxyethyl) isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. Examples of commercially available epoxy crosslinking agents include the trade names "Tetrad C" and "Tetrad X" manufactured by Mitsubishi Gas Chemical Company.
[0222] Examples of peroxides include dibenzoyl peroxide, dicumyl peroxide, di-t-butyl peroxide, di-t-butylperoxy-3,3,5-trimethylcyclohexane, t-butyl hydroperoxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexine-3, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-mono(t-butylperoxy)hexane, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, di(2-ethylhexyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, and t-butylperoxy Examples include neodecanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, di(4-methylbenzoyl) peroxide, t-butyl peroxyisobutyrate, 1,1-di(t-hexyl peroxy)cyclohexane, 1,1-di(t-butyl peroxy)cyclohexane, t-butyl peroxy-2-ethylhexyl carbonate, t-amyl peroxyisopropyl carbonate, 3,5,5-trimethylhexanoyl peroxide, t-butyl peroxy-2-hexanoate, t-butyl peroxypivalate, and t-hexyl peroxypivalate. Examples of commercially available peroxides include the "Nipper BMT" series and "Nipper BW" series manufactured by Nippon Oil & Fats Co., Ltd.
[0223] The thermosetting acrylic adhesive composition may contain an acrylic oligomer. The acrylic oligomer may be one type or two or more types. The description of the acrylic oligomer can be found in section [A-1-2-3. First Embodiment of Acrylic Adhesive (Photocuring Acrylic Adhesive)].
[0224] The thermosetting acrylic adhesive composition may contain any suitable other components as long as the effects of the present invention are not impaired. Examples of such other components include tackifiers, inorganic fillers, organic fillers, metal powders, pigments, colorants, foils, softeners, anti-aging agents, conductive agents, ultraviolet absorbers, antioxidants, light stabilizers, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, other crosslinking agents, solvents, catalysts, crosslinking catalysts, and crosslinking retardants.
[0225] <A-1-3. Antistatic layer> In addition to the base material layer and the adhesive layer, the adhesive film may have an antistatic layer. The antistatic layer can be provided, for example, on the side opposite to the adhesive layer of the base material layer, between the base material layer and the adhesive layer, or on the side opposite to the base material layer of the adhesive layer.
[0226] As the thickness of the antistatic layer, any appropriate thickness can be adopted as long as the effects of the present invention are not impaired. Such a thickness is preferably 1 nm to 1000 nm, more preferably 5 nm to 900 nm, still more preferably 7.5 nm to 800 nm, and particularly preferably 10 nm to 700 nm.
[0227] The antistatic layer may be only one layer or two or more layers.
[0228] As the antistatic layer, any appropriate antistatic layer can be adopted as long as it can exhibit an antistatic effect and the effects of the present invention are not impaired. Such an antistatic layer is preferably an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer on any appropriate base material layer. Specifically, for example, it is an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer on a resin base film. Specific coating methods include roll coating, bar coating, gravure coating, and the like.
[0229] As the conductive polymer, any suitable conductive polymer can be used as long as it does not impair the effects of the present invention. Examples of such conductive polymers include conductive polymers doped with polyanions in a π-conjugated conductive polymer. Examples of π-conjugated conductive polymers include chain-like conductive polymers such as polythiophene, polypyrrole, polyaniline, and polyacetylene. Examples of polyanions include polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyethyl sulfonic acid, and polymethacrylic acid. There may be only one conductive polymer or two or more conductive polymers.
[0230] ≪A-2. Peel-off Liner≫ The thickness of the release liner is preferably 1 μm to 300 μm, more preferably 10 μm to 200 μm, even more preferably 20 μm to 150 μm, particularly preferably 35 μm to 100 μm, and most preferably 50 μm to 80 μm, in order to better exhibit the effects of the present invention.
[0231] The release liner typically includes a resin-based film.
[0232] Examples of resin-based films include: plastic films made from polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); plastic films made from olefin resins with α-olefins as monomer components, such as polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA); plastic films made from polyvinyl chloride (PVC); plastic films made from vinyl acetate resins; plastic films made from polycarbonate (PC); and polyphenylene sulfide (PPS). Examples include: plastic films composed of: polyamide (nylon), all-aromatic polyamide (aramid), and other amide resins; plastic films composed of polyimide resins; plastic films composed of polyetheretherketone (PEEK); plastic films composed of olefin resins such as polyethylene (PE) and polypropylene (PP); and plastic films composed of fluorine resins such as polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, and chlorofluoroethylene-vinylidene fluoride copolymer.
[0233] The resin substrate film may consist of only one layer or two or more layers. The resin substrate film may also be stretched.
[0234] The resin substrate film may be surface-treated. Examples of surface treatments include corona treatment, plasma treatment, chromic acid treatment, ozone exposure, flame exposure, high-voltage electric shock exposure, ionizing radiation treatment, and coating with an undercoat.
[0235] The resin substrate film may contain any suitable additives, as long as they do not impair the effects of the present invention.
[0236] The release liner may have a release layer. When the release liner has a release layer, typically the side with the release layer is directly laminated onto the adhesive layer of the adhesive film.
[0237] The material used to form the release layer can be any suitable material, as long as it does not impair the effects of the present invention. Examples of such materials include silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, and fatty acid amide-based release agents. Among these, silicone-based release agents are preferred. The release layer can be formed as a coating layer.
[0238] The thickness of the release layer can be any appropriate thickness depending on the purpose, as long as it does not impair the effects of the present invention. Such a thickness is preferably 10 nm to 2000 nm, more preferably 10 nm to 1500 nm, even more preferably 10 nm to 1000 nm, and particularly preferably 10 nm to 500 nm.
[0239] The release layer may consist of only one layer or two or more layers.
[0240] Examples of silicone-based release layers include addition-reaction type silicone resins. Specifically, examples of addition-reaction type silicone resins include KS-774, KS-775, KS-778, KS-779H, KS-847H, and KS-847T from Shin-Etsu Chemical Co., Ltd.; TPR-6700, TPR-6710, and TPR-6721 from Toshiba Silicone Co., Ltd.; and SD7220 and SD7226 from Toray Dow Corning Co., Ltd. The amount of silicone-based release layer applied (after drying) is preferably 0.01 g / m². 2 ~2g / m 2 More preferably 0.01 g / m 2 ~1g / m 2 And more preferably 0.01 g / m 2 ~0.5g / m 2 That is the case.
[0241] The release layer can be formed, for example, by applying the above-mentioned forming material onto any appropriate layer by a conventionally known coating method such as reverse gravure coating, bar coating, die coating, etc., and then usually curing it by heat treatment at about 120 to 200 °C. Further, heat treatment and irradiation with active energy rays such as ultraviolet irradiation may be used in combination as necessary.
[0242] The release liner may have an antistatic layer.
[0243] Regarding the antistatic layer, the description in the section <A-1-3. Antistatic layer> can be incorporated.
[0244] One embodiment of the release liner includes a resin base film and a release layer in this order. Typically, this embodiment consists of a resin base film and a release layer.
[0245] Another embodiment of the release liner includes a resin base film, an antistatic layer, and a release layer in this order. Typically, this embodiment consists of a resin base film, an antistatic layer, and a release layer.
[0246] Still another embodiment of the release liner includes an antistatic layer, a resin base film, an antistatic layer, and a release layer in this order. Typically, this embodiment consists of an antistatic layer, a resin base film, an antistatic layer, and a release layer.
[0247] ≪A-3. Protective Film≫ As the protective film, any appropriate protective film can be adopted as long as the effects of the present invention are not impaired. Typically, such a protective film is a protective film having an adhesive layer on at least one side of a base film, and a protective film known as an optical surface protective film can be preferably adopted.
[0248] On the surface of the adhesive layer of the protective film, a release liner may be provided as necessary. Regarding the release liner, the description in the section ≪A-2. Release Liner≫ can be incorporated.
[0249] The thickness of the base film is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, even more preferably 10 μm to 100 μm, particularly preferably 15 μm to 80 μm, and most preferably 20 μm to 60 μm. The effects of the present invention can be more fully realized when the thickness of the base film is within the above range.
[0250] The thickness of the adhesive layer is preferably 1 μm to 250 μm, more preferably 2 μm to 150 μm, even more preferably 3 μm to 100 μm, particularly preferably 5 μm to 50 μm, and most preferably 7 μm to 30 μm. The effects of the present invention can be more fully realized when the thickness of the adhesive layer is within the above range.
[0251] Preferably, the base film and adhesive layer are those that can be used in protective films known as optical surface protective films, and for example, the description of the base film and adhesive layer in Japanese Patent Application Publication No. 2018-109092 can be used as reference.
[0252] <<<B. Manufacturing of Reinforcement Film>>> The reinforcing film according to the embodiment of the present invention can be manufactured by any suitable method, as long as the effects of the present invention are not impaired.
[0253] As a representative example of a method for manufacturing a reinforcing film according to an embodiment of the present invention, we will describe a case in which the reinforcing film according to an embodiment of the present invention has a release liner, two adhesive films, and a protective film in this order, and the two adhesive films, adhesive film (I) and adhesive film (II), are arranged with a gap between them.
[0254] One embodiment of the method for manufacturing a reinforcing film according to an embodiment of the present invention involves manufacturing a laminate (X) having two adhesive films on one release liner and a protective film, and then attaching the substrate layer side of the laminate (X) to one of the protective films and the adhesive layer side of the protective film.
[0255] The laminate (X) can be manufactured by, for example, applying an adhesive composition (typically an acrylic adhesive composition) that forms the adhesive that constitutes the adhesive layer of the adhesive film onto a substrate layer, heating and drying as necessary, and curing as necessary to form the adhesive layer on the substrate layer. A release liner (or the side with a release layer, if present) can be attached to the side of the adhesive layers (I) and (II) of the two adhesive films (I) and (II) obtained in this way that is opposite to the substrate layers (I) and (II), so that the two adhesive films (I) and (II) are arranged with a gap between them.
[0256] The protective film is manufactured, for example, by applying an adhesive composition that forms the adhesive that constitutes the adhesive layer onto a base film, heating and drying as necessary, and curing as necessary to form the adhesive layer on the base film.
[0257] Until the laminate (X) and the protective film are bonded together, any suitable release liner may be applied to protect the exposed surface of the adhesive layer of the protective film.
[0258] <<<C. Uses of Reinforcement Film>>> The reinforcing film according to the embodiment of the present invention can be used in any suitable application. The reinforcing film according to the embodiment of the present invention is preferably used, for example, to reinforce optical components and electronic components. Examples of optical components include LCDs, touch panels using LCDs, color filters used in LCDs, polarizing plates, and the like.
[0259] The optical and electronic components mentioned above may be flexible devices such as bendable devices, foldable devices, or rollable devices, each having a movable bending portion. [Examples]
[0260] The present invention will be specifically described below with reference to examples, but the present invention is not limited in any way to these examples. The test and evaluation methods in the examples are as follows. When "parts" is written, it means "parts by weight" unless otherwise specified, and when "%" is written, it means "percent by weight" unless otherwise specified.
[0261] <Measurement of flexion recovery angle> The release liner was peeled off the adhesive film with a release liner that had been prepared, and the sample was attached to a polyimide film (Ube Industries, UPILEX25RN) and cut to TD80mm x MD25mm. The cut sample was wrapped around a 3mm thick glass made by stacking two 1.5mm thick glass pieces, with the polyimide film side facing outwards. Tape was used to secure the sample and glass together to prevent any gaps. After storing the prepared sample at 85°C for 48 hours, it was removed from the glass, and the bending recovery angle of the sample was measured with a protractor.
[0262] <Measurement of light transmittance at 550nm> The adhesive film with a release liner that was prepared was cut to TD20mm x MD50mm. The release liner was peeled off the cut adhesive film, and the transmittance was measured using a Hitachi High-Technologies Corporation "U4100 spectrophotometer". The measurement condition was the transmittance at 550nm.
[0263] <Measurement of Storage Modulus G'> The storage modulus G' corresponds to the portion of elastic energy stored when a material deforms, and is an indicator of its degree of hardness. Only the adhesive layer of the adhesive film was extracted, laminated to a thickness of approximately 1 mm, and then punched out to a diameter of φ8 mm to create cylindrical pellets, which were used as measurement samples. A dynamic viscoelasticity measuring device (DHR, manufactured by T.A. Instruments) was used to obtain measurement samples, which were then fixed to a φ8 mm parallel plate jig, and the storage modulus G' was calculated. The measurement conditions were as follows. Measurement: Shear mode Temperature range: -60°C to 200°C Heating rate: 5°C / min Frequency: 1 Hz
[0264] <Measurement of Adhesion to Glass> The adhesive film with the prepared release liner was cut into TD25 mm × MD100 mm. The release liner was peeled off from the cut adhesive film with the release liner, and it was attached to glass (manufactured by Matsunami Glass, S2004U8) with a 2 kg roller for one round trip. The obtained evaluation sample was stored at room temperature for 30 minutes and then measured with a tensile tester. As the tensile tester, the product named "Autograph AG-Xplus HS 6000 mm / min High-Speed Model (AG-50NX plus)" manufactured by Shimadzu Corporation was used. After setting the evaluation sample in the tensile tester, the tensile test was started. The conditions of the tensile test were a peeling angle of 180 degrees and a peeling speed (tensile speed) of 300 mm / min. The load when peeling the adhesive film from the above glass was measured, and the average load at that time was taken as the adhesion force.
[0265] <Measurement of Release Force (A) of Release Liner> The adhesive film with the prepared release liner was cut into TD50 mm × MD100 mm to make a sample. Double-sided tape No. 31B (manufactured by Nitto Denko) was pasted on the glass, and the one obtained by pasting the base material layer surface of the obtained sample and the glass together was used as the evaluation sample, and the release force of the release liner was measured with a tensile tester. As the tensile tester, the product named "Autograph AG-Xplus HS 6000 mm / min High-Speed Model (AG-50NX plus)" manufactured by Shimadzu Corporation was used. After setting the evaluation sample in the tensile tester, the tensile test was started. The conditions of the tensile test were a peeling angle of 180 degrees and a peeling speed (tensile speed) of 300 mm / min. The load when peeling the release liner from the adhesive film was measured, and the average load at that time was taken as the release force (A) of the release liner. The numerical values described in the table are the values converted to the measured values per 25 mm width.
[0266] <Measurement of Release Force (B) of Protective Film> The produced protective film was cut into TD 25 mm × MD 100 mm. The release liner of the produced adhesive film with a release liner was peeled off and attached to glass (manufactured by Matsunami Glass, S2004U8). The release liner of the above protective film was peeled off and pasted on the base material layer surface of the adhesive film with a 2 kg roller reciprocated once to be used as an evaluation sample. After storing at room temperature for 30 minutes, the peel strength of the protective film was measured with a tensile tester. As the tensile tester, the product name "Autograph AG-Xplus HS 6000 mm / min high-speed model (AG-50NX plus)" manufactured by Shimadzu Corporation was used. After setting the evaluation sample in the tensile tester, the tensile test was started. The conditions of the tensile test were a peel angle of 180 degrees and a peel speed (tensile speed) of 300 mm / min. The load when peeling the protective film from the adhesive film was measured, and the average load at that time was taken as the peel strength (B) of the protective film.
[0267] [Production Example 1]: Production of the adhesive layer (1) <Production of the acrylic adhesive composition (1)> 2-Ethylhexyl acrylate (2EHA) as a monomer component: 63 parts by weight, N-vinyl-2-pyrrolidone (NVP): 15 parts by weight, methyl methacrylate (MMA): 9 parts by weight, 2-hydroxyethyl acrylate (HEA): 13 parts by weight, 2,2'-azobisisobutyronitrile as a polymerization initiator: 0.2 parts by weight, and ethyl acetate as a polymerization solvent: 133 parts by weight were charged into a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing the oxygen in the polymerization system in this way, the temperature was raised to 65 °C and reacted for 5 hours, then the temperature was raised to 70 °C and reacted for 2 hours, and ethyl acetate was added to obtain a solution of an acrylic polymer (1) with a solid content concentration of 30% by weight. The weight average molecular weight of the acrylic polymer (1) was 800,000. Next, an isocyanate crosslinking agent (trade name "Takenate D110N", manufactured by Mitsui Chemicals, Inc.) was added to the solution of the acrylic polymer (l) so as to be 1.1 parts by weight in terms of solid content per 100 parts by weight of the acrylic polymer (1) (solid content), and this was mixed to produce the acrylic adhesive composition (1). <Manufacturing of adhesive layer (1)> A 50 μm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical's "MRV50T100J") with a silicone-based release layer on its surface was used as a release liner (1a) (double-layer release film), and the above-mentioned acrylic adhesive composition (1) was applied to the release liner (1a) to a thickness of 13 μm to form a coating layer. Next, the release liner (1a) with the coating layer formed was placed in an oven and dried at 130°C for 1 minute. Then, a 50 μm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical's "MRQ50T100J") with a silicone-based release layer on its surface was used as a release liner (1b) to protect the surface of the coating layer, and a 13 μm thick adhesive layer (1) was manufactured as a laminate (1) of release liner (1a) / adhesive layer (1) / release liner (1b). The properties of the adhesive layer (1) are shown in Table 1.
[0268] [Manufacturing Example 2]: Manufacturing of the adhesive layer (2) <Prepolymer composition (2) production> A prepolymer composition (2) (polymerization rate: approximately 10%) was obtained by blending 60 parts by weight of lauryl acrylate (LA), 22 parts by weight of 2-ethylhexyl acrylate (2EHA), 8 parts by weight of 4-hydroxybutyl acrylate (4HBA), 10 parts by weight of N-vinyl-2-pyrrolidone (NVP) as monomer components for prepolymer formation, and 0.01 parts by weight of BASF's "Irgacure 184" and 0.01 parts by weight of BASF's "Irgacure 651" as photopolymerization initiators, and polymerization was carried out by irradiation with ultraviolet light. <Manufacturing of acrylic oligomers> 60 parts by weight of dicyclopentanyl methacrylate (DCPMA) and 40 parts by weight of methyl methacrylate (MMA) as monomer components, 3.4 parts by weight of α-thioglycerol as a chain transfer agent, and ethyl acetate as a polymerization solvent were mixed to a concentration of 60% and stirred at 70°C for 1 hour under a nitrogen atmosphere. Next, 0.2 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) was added as a thermal polymerization initiator and the mixture was reacted at 70°C for 2 hours. Subsequently, 0.1 parts of AIBN were added, and the temperature was raised to 80°C and the mixture was reacted for 2 hours to obtain an acrylic oligomer solution. Next, the acrylic oligomer solution was dried at 85°C to obtain an acrylic oligomer powder. The weight-average molecular weight of the acrylic oligomer was 5100, and the glass transition temperature (Tg) was 130°C. <Manufacturing of acrylic adhesive composition (2)> To 100 parts by weight of the above prepolymer composition (2), 37 parts by weight of 2-ethylhexyl acrylate (2EHA), 0.08 parts by weight of 1,6-hexanediol diacrylate (HDDA), 6 parts by weight of the above acrylic oligomer, and 0.3 parts by weight of a silane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM403") were added as post-addition components, and these were then uniformly mixed to produce acrylic adhesive composition (2). <Manufacturing of adhesive layer (2)> A 75 μm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical's "Diafol MRF75") with a silicone-based release layer on its surface was used as a release liner (2a) (also serving as a heavy-duty release film), and the above-mentioned acrylic adhesive composition (2) was applied to the release liner (2a) to a thickness of 15 μm to form a coating layer. On the formed coating layer, a 75 μm thick PET film (Mitsubishi Chemical's "Diafol MRE75") with one side treated with silicone release treatment was laminated as a cover sheet (also serving as a light-release film) as a release liner (2b). The resulting laminate was subjected to an irradiation intensity of 5 mW / cm² at the irradiation surface directly beneath the lamp, from the cover sheet side. 2Using a black light positioned to achieve this, ultraviolet light was irradiated to perform photocuring, and a 15 μm thick adhesive layer (2) was manufactured as a laminate (2) of a release liner (2a) / adhesive layer (2) / release liner (2b). The properties of the adhesive layer (2) are shown in Table 1.
[0269] [Table 1]
[0270] [Manufacturing Example 3] (Manufacturing of adhesive film (1)) As a binder, 100 parts by weight of a 25% aqueous solution of polyester resin (Toyobo Co., Ltd., trade name "Byronal MD-1480"), 20 parts by weight of a conductive polymer, and 5 parts by weight of a melamine-based crosslinking agent (Sumitomo Chemical Co., Ltd., trade name "Sumimar M-50W") were added to a mixed solvent of water / ethanol (1 / 1 by weight ratio) and stirred for about 20 minutes to mix thoroughly. In this way, a coating material (X) with a solid content of approximately 0.4% was prepared. As the conductive polymer, an aqueous solution containing 0.5% poly(3,4-ethylenedioxythiophene) (PEDOT) and 0.8% polystyrene sulfonate (weight-average molecular weight 150,000) (PSS) (Bytron P, HCStark) was used. A polyimide (PI) substrate (UPI50RN, manufactured by Ube Industries, Ltd.) with a thickness of 50 μm was coated with the above coating material (X) using a bar coater, and dried by heating at 130°C for 2 minutes to produce a substrate with an antistatic layer having a transparent antistatic layer with a thickness of 40 nm on one side. An adhesive layer (1) obtained by peeling off the release liner (1b) from the laminate (1) obtained in Manufacturing Example 1 was attached to the side of the fabricated antistatic layer substrate opposite to the antistatic layer using a hand roller, and heated and pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (1) with a release liner (1a).
[0271] [Manufacturing Example 4] (Manufacturing of adhesive film (2)) A polyimide (PI) substrate (UPI50RN, manufactured by Ube Industries, Ltd.) with a thickness of 50 μm was coated with the coating material (X) prepared in Manufacturing Example 3 using a bar coater on one side, and then heated at 130°C for 2 minutes to dry, thereby producing a substrate with an antistatic layer having a transparent antistatic layer with a thickness of 40 nm on one side. An adhesive layer (2) obtained by peeling off the release liner (2b) from the laminate (2) obtained in Manufacturing Example 2 was attached to the side of the fabricated antistatic layer substrate opposite to the antistatic layer using a hand roller, and the two layers were heated and pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (2) with a release liner (2a).
[0272] [Manufacturing Example 5] (Manufacturing of adhesive film (3)) A 40 μm thick triacetylcellulose (TAC) substrate (Fujifilm Corporation's "ZRD40SL (ZRG)") was coated with the coating material (X) prepared in Manufacturing Example 3 using a bar coater on one side, and then heated at 130°C for 2 minutes to dry, thereby producing a substrate with an antistatic layer having a 40 nm thick transparent antistatic layer on one side of the substrate. An adhesive layer (1) obtained by peeling off the release liner (1b) from the laminate (1) obtained in Manufacturing Example 1 was attached to the side of the fabricated antistatic layer substrate opposite to the antistatic layer using a hand roller, and heated and pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (3) with a release liner (1a).
[0273] [Manufacturing Example 6] (Manufacturing of adhesive film (4)) A 40 μm thick triacetylcellulose (TAC) substrate (Fujifilm Corporation's "ZRD40SL (ZRG)") was coated with the coating material (X) prepared in Manufacturing Example 3 using a bar coater on one side, and then heated at 130°C for 2 minutes to dry, thereby producing a substrate with an antistatic layer having a 40 nm thick transparent antistatic layer on one side of the substrate. On the surface of the substrate with the antistatic layer opposite to the antistatic layer of the produced substrate with an antistatic layer, the adhesive layer (2) obtained by peeling off the release liner (2b) from the laminate (2) obtained in Production Example 2 was bonded using a hand roller, and heat-pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (4) with a release liner (2a).
[0274] [Production Example 7] (Production of Adhesive Film (5)) On one side of a polyethylene terephthalate (PET) substrate (thickness 50 μm, "T100C50" manufactured by Mitsubishi Chemical Corporation, hereinafter sometimes referred to as PET50) as the base material layer, the coating material (X) prepared in Production Example 3 was applied using a bar coater, and heated at 130°C for 2 minutes to dry, thereby producing a substrate with an antistatic layer having a transparent antistatic layer with a thickness of 40 nm on one side of the substrate. On the surface of the substrate with the antistatic layer opposite to the antistatic layer of the produced substrate with an antistatic layer, the adhesive layer (1) obtained by peeling off the release liner (1b) from the laminate (1) obtained in Production Example 1 was bonded using a hand roller, and heat-pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (5) with a release liner (1a).
[0275] [Production Example 8] (Production of Adhesive Film (6)) On one side of a polyethylene terephthalate (PET) substrate (thickness 50 μm, "T100C50" manufactured by Mitsubishi Chemical Corporation, hereinafter sometimes referred to as PET50) as the base material layer, the coating material (X) prepared in Production Example 3 was applied using a bar coater, and heated at 130°C for 2 minutes to dry, thereby producing a substrate with an antistatic layer having a transparent antistatic layer with a thickness of 40 nm on one side of the substrate. On the surface of the substrate with the antistatic layer opposite to the antistatic layer of the produced substrate with an antistatic layer, the adhesive layer (2) obtained by peeling off the release liner (2b) from the laminate (2) obtained in Production Example 2 was bonded using a hand roller, and heat-pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (6) with a release liner (2a).
[0276] [Production Example 9] (Manufacturing of adhesive film (7)) A polyethylene terephthalate (PET) substrate (T100-75S, manufactured by Mitsubishi Chemical Corporation) with a thickness of 75 μm (hereinafter sometimes referred to as PET75) was coated with the coating material (X) prepared in Manufacturing Example 3 using a bar coater on one side, and dried by heating at 130°C for 2 minutes to produce a substrate with an antistatic layer having a transparent antistatic layer with a thickness of 40 nm on one side. An adhesive layer (1) obtained by peeling off the release liner (1b) from the laminate (1) obtained in Manufacturing Example 1 was attached to the side of the fabricated antistatic layer substrate opposite to the antistatic layer using a hand roller, and heated and pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (7) with a release liner (1a).
[0277] [Manufacturing Example 10] (Manufacturing of adhesive film (8)) A polyethylene terephthalate (PET) substrate (T100-75S, manufactured by Mitsubishi Chemical Corporation) with a thickness of 75 μm (hereinafter sometimes referred to as PET75) was coated with the coating material (X) prepared in Manufacturing Example 3 using a bar coater on one side, and dried by heating at 130°C for 2 minutes to produce a substrate with an antistatic layer having a transparent antistatic layer with a thickness of 40 nm on one side. An adhesive layer (2) obtained by peeling off the release liner (2b) from the laminate (2) obtained in Manufacturing Example 2 was attached to the side of the fabricated antistatic layer substrate opposite to the antistatic layer using a hand roller, and heated and pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (8) with a release liner (2a).
[0278] [Manufacturing Example 11] (Manufacturing of protective films) 100 parts by weight of 2-ethylhexyl acrylate (2EHA) and 4 parts by weight of 2-hydroxyethyl acrylate (HEA) as monomer components, 0.2 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator, and 182 parts by weight of ethyl acetate as a polymerization solvent were placed in a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, the temperature was raised to 60°C and the reaction was carried out for 4.5 hours, and then the temperature was raised to 70°C and the reaction was carried out for another 4.5 hours to obtain a solution of acrylic polymer with a solid content of 35.5% by weight. The weight-average molecular weight of the acrylic polymer was 800,000. To 100 parts by weight of the obtained acrylic polymer, 0.03 parts by weight of a tin catalyst (Envirizer OL-1, manufactured by Tokyo Fine Chemical Co., Ltd.), 5 parts by weight of an isocyanate crosslinking agent (Coronate HX, manufactured by Nippon Polyurethane Industries Co., Ltd.), 0.3 parts by weight of a surfactant (Aqualon HS-10, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), toluene as a solvent, and acetylacetone as a crosslinking retarder were mixed to a solution concentration of 20% to prepare an adhesive solution. Acetylacetone was added in an amount of 5 parts by weight relative to the amount of solvent. The obtained adhesive solution was coated onto a 50 μm thick PET film (Mitsubishi Chemical's "T100C50"), dried at 130°C for 1 minute, and then a 50 μm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical's "MRQ50T100J") was laminated as a release liner to create a protective film. The thickness of the adhesive layer was 10 μm.
[0279] [Example 1] A 50 μm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical's "MRQ50T100J") (150 mm x 70 mm in size) was used as a release liner. On this film, two adhesive films were used: adhesive film (I), cut to a size of 134 mm x 70 mm (2); and adhesive film (II), cut to a size of 15 mm x 70 mm (5). These films were bonded together in the arrangement shown in Figure 2, with their respective vertical and horizontal directions parallel, and a 1 mm gap between the horizontal edges of adhesive film (I) and adhesive film (II), with the adhesive layer of each film facing the release liner. Before bonding, the release liners on each adhesive film were removed. Next, the protective film obtained in manufacturing example 11 was cut to a size of 150 mm in length and 70 mm in width, and was attached to the base material layer side of each adhesive film so that it overlapped the release liner when viewed from the planar direction. As a result, a reinforcing film (1) is obtained in which two adhesive films (2) and (5) are arranged with a gap between them and one release liner and one protective film. The results are shown in Table 2. Furthermore, Table 3 shows the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (I), and the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (II).
[0280] [Examples 2-10] Reinforcement films (2) to (10) were obtained in the same manner as in Example 1, except that the types of adhesive film used as adhesive film (I) and adhesive film used as adhesive film (II) were changed as shown in Table 2. The results are shown in Table 2. Furthermore, Table 3 shows the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (I), and the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (II).
[0281] [Comparative Examples 1-10] Reinforcement films (C1) to (C10) were obtained in the same manner as in Example 1, except that the types of adhesive film used as adhesive film (I) and adhesive film used as adhesive film (II) were changed as shown in Table 2. The results are shown in Table 2. Furthermore, Table 3 shows the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (I), and the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (II).
[0282] [Table 2]
[0283] [Table 3] [Industrial applicability]
[0284] The reinforcing film according to the embodiment of the present invention can be suitably used, for example, for reinforcing optical components. The reinforcing film according to the embodiment of the present invention can be suitably used in flexible devices such as bendable devices, foldable devices, and rollable devices having movable bending portions. [Explanation of symbols]
[0285] 1000 Reinforcement Film 100 release liners 200 protective films 300a adhesive film 300b Adhesive Film 300c adhesive film 10a Base material layer 10b Base material layer 20a Adhesive layer 20b Adhesive layer
Claims
1. A reinforcing film in which two or more PSA films are arranged with a gap between one release liner and one protective film, Each of the two or more adhesive films includes a base layer and an adhesive layer, the pressure-sensitive adhesive layers of the two or more pressure-sensitive adhesive films are directly laminated to the one release liner; The two or more PSA films include at least one PSA film (I) having a flex recovery angle of 35 degrees or more and at least one PSA film (II) having a light transmittance of 80% or more at 550 nm; Reinforcement film.
2. The pressure-sensitive adhesive layer of the pressure-sensitive adhesive film (I) has a storage modulus at 85° C. of 1.0×10 5 The reinforced film of claim 1 , wherein the elastic modulus is less than 100 Pa.
3. The pressure-sensitive adhesive layer of the pressure-sensitive adhesive film (II) has a storage modulus at 170° C. of 5.0×10 3 Pa or more 5.0×10 5 The reinforced film according to claim 1 or 2, wherein the elastic modulus is less than Pa.
4. The reinforcing film according to claim 1 , wherein the area of the adhesive film (I) is larger than the area of the adhesive film (II).
5. The reinforcing film according to claim 1 , which is a reinforcing film for optical members.
